Carbon nanotube dispersion composition, mixture slurry, electrode film, and secondary battery

JP2025036305AActive Publication Date: 2025-03-14TOYO INK MFG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024146556
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2024-08-28
Publication Date
2025-03-14
Estimated Expiration
2044-08-28

AI Technical Summary

Benefits of technology

【0015】 本発明の実施形態によれば、特に二次電池の寿命性能向上などが期待できる粒度分布範囲を有するカーボンナノチューブ分散組成物において、優れた流動性と保存安定性とを提供することが可能となる。また、このカーボンナノチューブ分散組成物を用いることで、サイクル特性とレート特性とを両立した二次電池を提供することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036305000001
    Figure 2025036305000001
  • Figure 2025036305000002
    Figure 2025036305000002
  • Figure 2025036305000003
    Figure 2025036305000003
Patent Text Reader

Abstract

To provide a carbon nanotube dispersion composition that exhibits excellent cycle characteristics when used in a secondary battery while having both fluidity and storage stability; and a secondary battery that has both cycle characteristics and rate characteristics by employing the dispersion composition.SOLUTION: A carbon nanotube dispersion composition contains carbon nanotubes (A), a dispersant (B), and a solvent (C), where a particle diameter D50 at 50% cumulative volume by laser diffraction particle size distribution measurement is 0.3-7 μm. The composition satisfies (1) and (2): (1) the dispersant (B) is a polymer having weight-average molecular weight from 5,000 to 360,000 inclusive and having a carboxyl group-containing structural unit derived from at least one of (meth)acrylic acid and a (meth)acrylate having a carboxyl group, where a content of the carboxyl group-containing structural unit is 80 mass% or more based on mass of the polymer; and (2) if X [μm] refers to the particle diameter D50 at 50% cumulative volume by laser diffraction particle size distribution measurement of the carbon nanotube dispersion composition and Y refers to the pH, then X and Y satisfy (formula a) Y≥-0.149X+4.545 and (formula b) Y≤-0.134X+5.140.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a carbon nanotube dispersion composition. More specifically, the present disclosure relates to a carbon nanotube dispersion composition, a composite slurry containing the carbon nanotube dispersion composition and an active material, an electrode film formed from the composite slurry, and a secondary battery including the electrode film. [Background technology]

[0002] With the spread of electric vehicles and the trend toward smaller, lighter, and more powerful portable devices, there is a demand for secondary batteries with high energy density and for these batteries to have higher capacities. Under these circumstances, secondary batteries using non-aqueous electrolytes, particularly lithium-ion secondary batteries, are being used in many devices due to their characteristics of high energy density and high voltage.

[0003] Since the capacity of a lithium-ion secondary battery depends greatly on the main materials, that is, the positive electrode active material and the negative electrode active material, various materials for use as these electrode active materials have been actively researched. However, the charge capacity obtained when using electrode active materials in practical use has reached a level close to the theoretical value, and improvement of electrode active materials is close to the limit. Under such circumstances, silicon-based active materials that can reversibly dope more lithium ions than current graphite powder are expected as negative electrode active materials. However, when silicon-based active materials are used, cracks or particle isolation are likely to occur due to volume changes when absorbing and releasing lithium ions during charging and discharging, and there is a problem that the capacity decreases with repeated charging and discharging.

[0004] In addition, a technology using carbon nanotubes as a conductive material is being considered to improve the conductivity of the electrodes. The use of carbon nanotubes is expected to reduce the electrode resistance. In particular, when carbon nanotubes are used in the negative electrode, it is expected that the silicon-based active material, which has low conductivity, will be prevented from being electrically isolated due to the volume change caused by the absorption and release of lithium ions during charging and discharging, thereby improving the life of the battery.

[0005] In recent years, the use of a carbon nanotube dispersion has become the mainstream method for adding carbon nanotubes to composite slurries for secondary batteries. By setting the dispersed particle size of such a carbon nanotube dispersion within an appropriate range, it is possible to lay down conductive paths between active materials that store lithium ions.

[0006] For example, Patent Document 1 discloses a method for improving the cycle characteristics of a secondary battery by dispersing and stabilizing the carbon nanotube dispersion in a sodium carboxymethylcellulose aqueous solution containing multi-walled carbon nanotubes having an average fiber outer diameter in the range of 50 to 110 nm through specific particle size distribution characteristics, thereby improving the electrical conductivity. In Patent Document 2, the BET specific surface area is 70 to 250 m 2 A dispersion containing 2 to 15% by weight of carbon nanotube powder of 100 g / g at a temperature of 25°C and a shear rate of 383 s -1 The present invention discloses a method for providing a carbon nanotube dispersion liquid having excellent cycle characteristics by adjusting the viscosity at 2 to 110 mPa·s and the dispersed particle diameter d50 to 100 to 600 nm. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2016-028109 A [Patent Document 2] JP 2015-195143 A Summary of the Invention [Problem to be solved by the invention]

[0008] According to these methods, localization of the conductive material in the electrode due to entanglement of carbon nanotubes can be suppressed, and the conductive path can be maintained to improve cycle characteristics. However, carbon nanotubes are usually aggregates of entangled carbon fibers having nano-sized outer diameters. Since it is very difficult to defibrate and disperse these aggregates, it is difficult to obtain a carbon nanotube dispersion composition having high initial fluidity and excellent dispersion stability. In addition, when a carbon nanotube dispersion composition with poor fluidity is used, the diffusion of the conductive material becomes insufficient in the composite slurry obtained by further adding an active material, and when a coating film is formed, the internal resistance at high rates increases, and the rate characteristics become a problem.

[0009] Therefore, the present invention provides a carbon nanotube dispersion composition that has good cycle characteristics when used as a secondary battery, i.e., that has good fluidity and storage stability in a particle size range that results in a dispersion state of carbon nanotubes with excellent life performance. Also, by using the carbon nanotube dispersion composition, a secondary battery that has good cycle characteristics and rate characteristics is provided.

[0010] Furthermore, even when graphite powder and a silicon-based active material are used as the negative electrode active material, a secondary battery having excellent rate characteristics is provided. [Means for solving the problem]

[0011] That is, the present invention includes the following embodiments, but the embodiments of the present invention are not limited to the following. One embodiment includes carbon nanotubes (A), a dispersant (B), and a solvent (C), and has a particle size D at 50% cumulative volume measured by laser diffraction particle size distribution measurement. 50The present invention relates to a carbon nanotube dispersion composition having a particle size of 0.3 to 7 μm and satisfying the following (1) and (2): (1) The dispersant (B) is a polymer having a weight average molecular weight of 5,000 or more and 360,000 or less, and having a carboxyl group-containing structural unit derived from at least one of (meth)acrylic acid and a (meth)acrylate having a carboxyl group, The content of the carboxyl group-containing structural unit is 80 mass % or more based on the mass of the polymer. (2) Particle size D at 50% cumulative volume of the carbon nanotube dispersion composition measured by laser diffraction particle size distribution measurement 50 When X [μm] and pH is Y, X and Y satisfy the following (formula a) and (formula b). (Formula a) Y≧-0.149X+4.545 (Formula b) Y≦-0.134X+5.140 In the above embodiment, it is preferable that the carbon nanotube dispersion composition further contains a basic compound (D).

[0012] Another embodiment relates to a composite slurry containing the carbon nanotube dispersion composition of the above embodiment and an active material.

[0013] Another embodiment relates to an electrode film formed from the composite slurry of the above embodiment.

[0014] Another embodiment is a secondary battery including a positive electrode and a negative electrode, The present invention relates to a secondary battery in which at least one of a positive electrode and a negative electrode has the electrode film of the above embodiment. Effect of the Invention

[0015] According to the embodiment of the present invention, it is possible to provide excellent fluidity and storage stability in a carbon nanotube dispersion composition having a particle size distribution range that can be expected to improve the life performance of a secondary battery, etc. In addition, by using this carbon nanotube dispersion composition, it is possible to provide a secondary battery that achieves both cycle characteristics and rate characteristics.

[0016] Furthermore, when graphite powder and silicon-based active material are used as the negative electrode active material, even if the active material expands and contracts during charging and discharging, the carbon nanotubes are uniformly dispersed in the composite slurry, so that the conductive path is sufficiently maintained. This suppresses an increase in internal resistance within the electrode, suppresses a decrease in charge and discharge capacity, and makes it possible to provide a secondary battery with excellent rate characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The dispersion composition, the composite slurry, the electrode film, and the secondary battery, which are embodiments of the present invention, are described in detail below. The present invention is not limited to the following embodiments, and the present invention also includes embodiments that are implemented within the scope of the present invention. In this specification, any numerical range specified using "to" is intended to include the numerical values ​​before and after "to" as the lower and upper limit values ​​of the range.

[0018] In this specification, "carbon nanotubes" refers to "CNTs," "carbon nanotube dispersion composition" refers to "dispersion composition" or "CNT dispersion composition," and "particle size D at 50% cumulative volume measured by laser diffraction particle size distribution measurement" refers to 50 " to "Particle size D 50 " There are cases where this is said. In this specification, unless otherwise specified, the terms "(meth)acrylic", "(meth)acryloyl", "(meth)acrylic acid", "(meth)acrylate", and "(meth)acryloyloxy" respectively mean "acrylic or methacrylic", "acryloyl or methacryloyl", "acrylic acid or methacrylic acid", "acrylate or methacrylate", and "acryloyloxy or methacryloyloxy".

[0019] Unless otherwise noted, the various components described in this specification may be used independently as one type alone or as a mixture of two or more types. The numerical values ​​specified in this specification are values ​​determined by the methods disclosed in the embodiments or examples.

[0020] <1> Carbon nanotube dispersion composition The carbon nanotube dispersion composition of the present embodiment contains carbon nanotubes (A), a dispersant (B), and a solvent (C), Particle size D at 50% cumulative volume measured by laser diffraction particle size distribution measurement 50 is 0.3 to 7 μm, and satisfies the following (1) and (2). (1) The dispersant (B) is a polymer having a weight average molecular weight of 5,000 or more and 360,000 or less, and having a carboxyl group-containing structural unit derived from at least one of (meth)acrylic acid and a (meth)acrylate having a carboxyl group, The content of the carboxyl group-containing structural unit is 80 mass % or more based on the mass of the polymer. (2) Particle size D at 50% cumulative volume of the carbon nanotube dispersion composition measured by laser diffraction particle size distribution measurement 50 When X [μm] and pH is Y, X and Y satisfy the following (formula a) and (formula b). (Formula a) Y≧-0.149X+4.545 (Formula b) Y≦-0.134X+5.140

[0021] As described above, the present inventors have determined that the preferred pH range of the carbon nanotube dispersion composition is 50 For example, the particle size D 50 The larger the value, the lower the pH can be adjusted to improve storage stability and fluidity.

[0022] In the carbon nanotube dispersion composition of this embodiment, the dispersed particle size is the particle size D at 50% cumulative volume measured by laser diffraction particle size distribution measurement. 50 The particle size D is 0.3 to 7 μm. A carbon nanotube dispersion composition having such a particle size distribution range tends to easily provide a secondary battery having excellent cycle characteristics. 50is preferably 0.35 μm or more, and more preferably 0.4 μm or more. 50 is preferably 6 μm or less, more preferably 5.5 μm or less, and even more preferably 5 μm or less.

[0023] Particle size D 50 is correlated with the length of the carbon nanotubes in the dispersion composition, and the particle size D 50 In the carbon nanotube dispersion composition (hereinafter, also referred to as the dispersion composition) in which the particle diameter D is within the above range, the dispersion state of the carbon nanotubes in the dispersion composition is good, the cycle characteristics are excellent, and it is easy to extend the battery life. 50 If the particle size D exceeds the above range, the carbon nanotubes are in an aggregated state. 50 If the thickness is below the above range, a large amount of finely cut conductive material is produced, which tends to make it difficult to efficiently form a conductive network. Above particle size D 50 can be determined using a general laser diffraction particle size distribution measuring device using a dynamic light scattering method, but more specifically, can be measured by the method described in the Examples.

[0024] The pH of the carbon nanotube dispersion composition of this embodiment is in the range of "Y" defined by the above (formula a) and (formula b). The pH may be a value measured using, for example, a pH meter at 25°C. In some embodiments, the pH of the carbon nanotube dispersion composition is preferably in the range of 3.5 to 5.1, more preferably in the range of 3.8 to 5.0, when measured using a pH meter at 25°C. When the pH is within the above range, the dispersibility of the dispersant (B) can be easily improved, which tends to easily improve the fluidity and dispersion stability of the dispersion composition.

[0025] Thus, the carbon nanotube dispersion composition of this embodiment is a dispersion composition adjusted to a particle size distribution range that can be expected to produce a secondary battery with excellent cycle characteristics, and by using a dispersant (B) having a sufficient number of carboxyl groups and adjusting the pH of the dispersion composition to a specific range, it is possible to achieve both excellent fluidity and storage stability. Furthermore, even when an active material is added to the dispersion composition to form a composite slurry, the carbon nanotubes are uniformly distributed relative to the active material, thereby suppressing a decrease in capacity retention rate.

[0026] In order to obtain the carbon nanotube dispersion composition of this embodiment, it is preferable to apply a pH adjustment method so as to satisfy the range of "Y" defined in the above (formula a) and (formula b). The pH adjustment method is not particularly limited. For example, a method of adding a basic compound to the dispersion composition and adjusting the amount of the compound added, or a method of using carbon nanotubes that exhibit acidity or basicity can be mentioned. Carbon nanotubes that exhibit acidity can be obtained, for example, by a method of introducing an acidic functional group into carbon nanotubes by acid treatment or the like. Carbon nanotubes that exhibit basicity can be obtained, for example, by a method of adjusting the amount of metal derived from the catalyst remaining in the carbon nanotubes, or a method of pretreating carbon nanotubes with a basic compound (for example, a compound containing an alkali metal or an alkaline earth metal, an amine compound, etc.). In some embodiments, from the viewpoint of easy pH adjustment, the method of using a basic compound is preferred, and the method of adding a basic compound to the dispersion composition is more preferred. By adjusting the amount of the basic compound added, a desired pH value can be easily obtained. Details of the basic compound will be described later as "basic compound (D)".

[0027] In the dispersion composition of this embodiment, the dispersant (B) contains 80% by mass or more of a carboxyl group-containing structural unit. Therefore, the pH of a solution in which the dispersant (B) is dissolved in a solvent (e.g., water) capable of dissolving the dispersant (B) is acidic. More specifically, the pH value of the solution containing the dispersant (B) can be 2 or more and less than 7. The pH of the solution containing the dispersant (B) can be adjusted to reduce the COO- By generating a group (carboxylate anion), the particles can be dispersed and stabilized by the charge repulsion. For this reason, the present inventors determined that the particle size D at 50% cumulative volume, which is the dispersed particle size, in the carbon nanotube dispersion composition is determined by a laser diffraction particle size distribution measurement. 50 They have found that by controlling the relationship between the temperature and the pH, it is possible to lower the initial viscosity of the dispersion composition and achieve both the fluidity and dispersion stability of the dispersion composition.

[0028] Without being bound by theory, the above particle size D 50 The reason why there is a suitable range defined by the above formulae (formula a) and (formula b) in the relationship between the concentration and pH is as follows. First, the smaller the dispersed particle size, the faster the collision speed between particles due to Brownian motion. Therefore, in order to stabilize the dispersion, more COO - It is presumed that the repulsive force due to the charge repulsion of the COO groups is necessary. In other words, for example, when a basic compound is used to adjust the pH, the smaller the dispersed particle size, the more basic compound needs to be added, and as a result, the pH tends to be higher. In addition, in order to stabilize the dispersion, even when the dispersed particle size is large, - A certain level of electrical repulsion due to the groups is necessary. On the other hand, since carboxyl groups have a high affinity for carbon nanotubes (CNTs), dispersants containing many carboxyl groups are more likely to be adsorbed by CNTs. For example, if the pH becomes too high by adding an excess of a basic compound to the dispersion composition, the amount of carboxyl groups decreases relatively, and the dispersant may be detached from the CNTs. In particular, when the dispersed particle size is large, the mass of the CNT particles in the dispersion composition increases, so it is preferable to set the pH low. In this way, by appropriately adjusting the pH according to the size of the dispersed particle size and increasing the adsorption force of the dispersant to the carbon nanotubes, the particle repulsion force due to the osmotic pressure effect can be utilized, and as a result, it is considered that the storage stability and fluidity can be improved.

[0029] The carbon nanotube dispersion composition of this embodiment does not contain an active material. In this specification, when the carbon nanotube dispersion composition further contains an active material, it is defined as a composite slurry. That is, the dispersion composition of the present embodiment means a state before the active material is added to the dispersion composition. In these respects, the dispersion composition is distinguished from a composite slurry containing an active material. That is, the dispersion composition does not substantially contain an active material. The term "substantially does not contain" is a concept that excludes a state in which an active material is intentionally added to the dispersion composition. Specifically, the content of the active material may be 1 mass % or less, 0.5 mass % or less, or 0.1 mass % or less, or may be 0 mass %, based on the total mass of the dispersion composition. Details of the active material will be described later.

[0030] The dispersion composition of this embodiment can be suitably used to form an electrode for a secondary battery. However, the dispersion composition of this embodiment can be used not only for secondary batteries, but also for storage devices other than secondary batteries, such as electrodes for electric double layer capacitors and electrodes for non-aqueous electrolyte capacitors. In addition, it can be used for IC trays for plastic and rubber products, antistatic materials for molded bodies of electronic component materials, electronic components, transparent electrodes (ITO films) replacements, electromagnetic wave shields, and other applications.

[0031] The components of the carbon nanotube dispersion composition of this embodiment will be described below. <Carbon nanotubes (A)> The carbon nanotubes may be single-walled carbon nanotubes alone, multi-walled carbon nanotubes alone, or a mixture of single-walled carbon nanotubes and multi-walled carbon nanotubes. Single-walled carbon nanotubes have a structure in which one layer of graphite is wound, while multi-walled carbon nanotubes have a structure in which two or more layers of graphite are wound.

[0032] The average outer diameter of the carbon nanotubes used as the raw material is preferably 1 nm or more and 50 nm or less, more preferably 1 nm or more and 40 nm or less, or even more preferably 1 nm or more and 20 nm or less. In these ranges, the packing density of the active material in the electrode film can be further increased. By using carbon nanotubes in this range, bundles consisting of several CNTs can be formed in the dispersion composition, and a dispersion composition having the above-mentioned preferred average outer diameter after dispersion can be obtained.

[0033] The average outer diameter of the carbon nanotubes used as the raw material is calculated by the following method. First, carbon nanotubes are dispersed in toluene using an ultrasonic homogenizer, then the carbon nanotubes are placed on a collodion film and dried, and the carbon nanotubes are observed and photographed using a transmission electron microscope (TEM). Next, 100 carbon nanotubes are randomly selected from the observation photograph, and the outer diameter of each is measured. Next, the average outer diameter (nm) of the raw carbon nanotubes is calculated as the number average of the outer diameters.

[0034] The average fiber length of the carbon nanotubes used as a raw material is preferably 1 to 50 μm, and more preferably 1 to 20 μm. If it is within the above range, it is easy to adjust the fiber length to a preferred length after dispersion.

[0035] The fiber length of the carbon nanotubes used as raw material can be measured by dispersing the carbon nanotubes in toluene using an ultrasonic homogenizer, then depositing the carbon nanotubes on a mica substrate, observing them with an SEM, and analyzing the images. The SEM images are analyzed using the image analysis software "WinROOF2015" (Mitani Shoji), and the skeletal length of each carbon nanotube is calculated as the fiber length. The average of the fiber lengths of 1000 to 3000 carbon nanotubes is taken as the average fiber length of the carbon nanotubes used as raw material.

[0036] The BET specific surface area of ​​the carbon nanotubes used as the raw material, as measured by nitrogen adsorption, is 100 m 2 / g or more 1200m 2 When the BET specific surface area of ​​the carbon nanotubes is within the above range, the carbon nanotubes are easily distributed in the composite slurry when the carbon nanotubes are appropriately controlled to be dispersed, and the cycle performance can be further improved.

[0037] The carbon nanotubes used as the raw material have a Raman spectrum of 1560 to 1600 cm -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 When the maximum peak intensity within this range is D, the G / D ratio is preferably 0.5 or more and 100 or less, more preferably 0.8 or more and 50 or less, and further preferably 1 or more and 45 or less.

[0038] Among them, the specific surface area is 100m 2 / g or more 700m 2 When the G / D ratio is less than 1 / g, the G / D ratio is preferably 0.8 or more and 8 or less, and more preferably 0.8 or more and 5 or less. Specific surface area is 700m 2 / g or more 1200m 2 When the G / D ratio is 30 or more and 100 or less, the G / D ratio is preferably 30 or more and 100 or less, and more preferably 40 or more and 50 or less. It is preferable that the G / D ratio of the carbon nanotube is within the above range, since it is highly crystalline and easy to obtain good electrical conductivity. The preferable range differs depending on the specific surface area because when the specific surface area is small, it is mainly multi-walled CNTs, and the D band becomes strong due to the influence of terminal sp3 hybridized carbon and between layers, so the G / D ratio range for good electrical conductivity is smaller than that of high-specific surface area carbon nanotubes. When the specific surface area is high, it is mainly single-walled CNTs, and the loss of sp2 carbon can be inferred from the G / D ratio, and when it is within the above range, it is possible to show few losses and good electrical conductivity.

[0039] The volume resistivity of the carbon nanotubes used as the raw material is 1.0×10 -3 Ω cm or more 3.0×10 -2 It is preferable that the resistance is Ω·cm or less, and 1.0×10 -3Ω cm or more 1.0×10 -2 It is more preferable that the resistivity is Ω·cm or less. The volume resistivity of the carbon nanotubes can be measured using a powder resistivity measuring device (Loresta GP Powder Resistivity Measuring System MCP-PD-51, manufactured by Mitsubishi Chemical Analytech Co., Ltd.) When the volume resistivity of the carbon nanotubes is within the above range, the electron transfer resistance between the carbon nanotubes and the active material can be reduced.

[0040] The carbon purity of the carbon nanotubes used as the raw material is expressed as the content (%) of carbon atoms in the carbon nanotubes. The carbon purity is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, based on 100% by mass of the carbon nanotubes. When the carbon purity of the carbon nanotubes is within the above range, problems such as short circuits caused by the formation of dendrites due to impurities such as metal catalysts can be prevented.

[0041] The amount of metal contained in the carbon nanotubes used as raw material is preferably less than 20% by mass, more preferably less than 10% by mass, and even more preferably less than 5% by mass, based on 100% by mass of the carbon nanotubes. Metals contained in the carbon nanotubes include metals and metal oxides used as catalysts when synthesizing carbon nanotubes, and metal powders mixed in due to wear of the equipment. Specific examples include metals such as cobalt, nickel, aluminum, magnesium, silica, manganese, and molybdenum, alloys of these metals, metal oxides, and composite oxides of these metals.

[0042] The carbon purity and metal content in the carbon nanotubes can be determined by ICP emission spectrometry.

[0043] The carbon nanotubes used as the raw material may be surface-treated carbon nanotubes. The carbon nanotubes may also be carbon nanotube derivatives to which functional groups such as carboxyl groups have been added. Carbon nanotubes that encapsulate substances such as organic compounds and metal atoms may also be used.

[0044] The carbon nanotubes used as the raw material may be pulverized carbon nanotubes. The pulverization process is performed by using a pulverizer containing pulverization media such as beads and steel balls to pulverize the carbon nanotubes without the presence of any liquid substance, and is also called dry pulverization. The pulverization is performed by utilizing the pulverization force or destructive force caused by the collision between pulverization media. The pulverization mainly has the effect of reducing the size of the secondary particles of the carbon nanotubes, and can improve the dispersibility of the carbon nanotubes. As the dry pulverization device, a known method such as a dry attritor, ball mill, vibration mill, or bead mill can be used, and the pulverization time can be set arbitrarily depending on the device.

[0045] The carbon nanotubes used as the raw material may be carbon nanotubes produced by any method. Carbon nanotubes can generally be produced by a laser ablation method, an arc discharge method, a thermal CVD method, a plasma CVD method, or a combustion method, but are not limited to these.

[0046] <Dispersant (B)> The carbon nanotube dispersion composition of this embodiment contains a dispersant (B). The dispersant has a function of stabilizing the dispersion of CNTs in the dispersion composition, and other dispersants may be used in combination as long as the effect is not impaired. The dispersant (B) is a polymer having a weight average molecular weight of 5,000 or more and 360,000 or less and having a carboxyl group-containing structural unit, the content of the carboxyl group-containing structural unit being 80 mass % or more based on the mass of the polymer. By using such a dispersant (B) to disperse carbon nanotubes, it is possible to obtain a specific particle size D 50It is possible to easily obtain a carbon nanotube dispersion composition which satisfies the above requirements and has excellent fluidity and storage stability.

[0047] The weight average molecular weight of the dispersant (B) is 5,000 or more and 360,000 or less. The weight average molecular weight of the dispersant (B) is preferably 6,000 or more, more preferably 8,000 or more. Also, it is preferably 260,000 or less, more preferably 100,000 or less. In some embodiments, the weight average molecular weight of dispersant (B) may be preferably 9,000 or more, more preferably 10,000 or more, and even more preferably 50,000 or more. Also, the weight average molecular weight of dispersant (B) may be preferably 90,000 or less, more preferably 80,000 or less, and more preferably 70,000. When the weight average molecular weight is within this range, the adsorptivity to carbon nanotubes is improved, and the stability of the dispersion can be further improved.

[0048] The dispersant (B) is a polymer having a carboxyl group-containing structural unit, and the content of the carboxyl group-containing structural unit is 80 mass % or more based on the mass of the polymer. By having a sufficient number of carboxyl groups in the molecule, the compound has strong ionic properties, which enhances the adsorptivity to carbon nanotubes and the affinity to a medium, allowing the carbon nanotubes to exist stably in the medium. In some embodiments, the dispersant (B) is preferably a polymer of at least one of (meth)acrylic acid and (meth)acrylate having a carboxyl group. That is, the dispersant (B) is preferably a polymer containing a structural unit derived from at least one of (meth)acrylic acid and (meth)acrylate having a carboxyl group, and more preferably a polymer containing a structural unit derived from (meth)acrylic acid. When the above polymer is used as the dispersant (B), it is excellent in dispersibility of carbon nanotubes, and it is easy to further improve the rate characteristics and cycle characteristics as a battery material. The dispersant (B) is preferably a polymer having an alkylene structure in the main chain.

[0049] In this specification, the content of each structural unit of the dispersant can be calculated based on the mass% of the precursor (monomer) used during polymerization. Therefore, the content of the carboxyl group-containing structural unit described later means the content of (meth)acrylic acid and / or (meth)acrylate having a carboxyl group based on the total amount of the monomer used to produce the dispersant (polymer).

[0050] From the viewpoint of providing a suitable affinity with the solvent described later, the content of the carboxyl group-containing structural unit is preferably 90% by mass or more, and more preferably 95% by mass or more, when the mass of the polymer (excluding the initiator and the chain transfer agent) is taken as 100% by mass. On the other hand, the content may be 98% by mass or less. In one embodiment, the content may be 100% by mass. By having the content of 90% by mass or more, it is possible to expect better dispersion stabilization of the CNTs due to the charge repulsion of the carboxyl groups.

[0051] In one embodiment, the dispersant (B) may further contain one or more selected from the group consisting of a nitrile group-containing structural unit, a hydroxyl group-containing structural unit, and a heterocyclic ring-containing structural unit in addition to the carboxyl group-containing structural unit. In this way, when the dispersant (B) further contains one or more of the above structural units in addition to the carboxyl group-containing structural unit, it is preferable because the polarization becomes stronger and the affinity between the carbon nanotube and the medium becomes higher.

[0052] [Carboxyl group-containing structural unit] The carboxyl group-containing structural unit is a structural unit having a carboxyl group, and may be a structural unit having an alkylene structure substituted with a carboxyl group. The alkylene structure is preferably a linear or branched alkylene structure. The number of carboxyl groups that the carboxyl group-containing structural unit has is preferably 1 or 2, more preferably 1. The method of introducing a carboxyl group-containing structural unit into a polymer is not particularly limited. For example, a method of preparing a polymer by polymerization reaction of a monomer having a carboxyl group, more specifically (meth)acrylic acid or (meth)acrylate having a carboxyl group, etc., can be mentioned. As another method, a method of preparing a polymer by polymerization reaction of a monomer containing a functional group other than a carboxyl group, and then modifying the functional group to a carboxyl group can be mentioned. In particular, a method of preparing a polymer by polymerization reaction of a monomer having a carboxyl group can be preferably used.

[0053] Examples of monomers having a carboxyl group include unsaturated fatty acids such as (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, and citraconic acid, and (meth)acrylates having a carboxyl group such as 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxypropyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxypropyl hexahydrophthalate, ethylene oxide-modified succinic acid (meth)acrylate, and β-carboxyethyl (meth)acrylate. In addition, examples of monomers having a carboxyl group include monomers having an acid anhydride group such as maleic anhydride, itaconic anhydride, and citraconic anhydride, which are polymers of the monomers having a carboxyl group, and monofunctional alcohol adducts thereof.

[0054] A group having a structure in which two carboxyl groups are dehydrated and condensed, "-C(=O)-OC(=O)-" (herein referred to as an "acid anhydride group"), also forms a carboxyl group upon hydrolysis. Therefore, in this specification, it is included in the concept of a carboxyl group. In addition, a carboxyl group-containing structural unit may be obtained by hydrolyzing the carbamoyl group of a polymer obtained by polymerization reaction of a monomer having a carbamoyl group, such as (meth)acrylamide.

[0055] As the monomer having a carboxyl group, which is a precursor of the carboxyl group-containing structural unit, from the viewpoint of electrochemical stability, an unsaturated fatty acid is preferable, (meth)acrylic acid is more preferable, and acrylic acid is even more preferable. Acrylic acid is preferable because it has excellent solubility in water and dispersibility of carbon nanotubes, and can further improve the rate characteristics and cycle characteristics as a battery material.

[0056] [Nitrile group-containing structural unit] The nitrile group-containing structural unit is a structural unit having a nitrile group, and may be a structural unit having an alkylene structure substituted with a nitrile group. The alkylene structure is preferably a linear or branched alkylene structure. The number of nitrile groups contained in the nitrile group-containing structural unit is preferably one or two, and more preferably one. The method for introducing the nitrile group-containing structural unit into the dispersant is not particularly limited. In one embodiment, for example, a polymer can be prepared by a polymerization reaction of a monomer having a nitrile group.

[0057] Examples of monomers having a nitrile group include acrylonitrile, methacrylonitrile, and fumaronitrile. These can be used alone or in combination of two or more. When the monomer having a nitrile group is acrylonitrile, the copolymer is less bent, and adjacent cyano groups are oriented to form a partial structure with strong polarization. Therefore, the intermolecular force between polymers or between a polymer and a carbon-based conductive material is high. From the viewpoint of increasing the intermolecular force as described above, as well as the ease of obtaining raw materials and reactivity, it is preferable that the monomer having a nitrile group is acrylonitrile. From the viewpoint of increasing the intermolecular force, the content of the nitrile group-containing structural unit is preferably 3% by mass or more, more preferably 5% by mass or more, when the mass of the polymer is taken as 100% by mass, while it is preferably 20% by mass or less, more preferably 10% by mass or less. By adjusting the content of the nitrile group-containing structural unit to the above range, the carbon nanotube can be more stably present in the medium. In addition, when such a polymer is used in a secondary battery, it is preferable because it can prevent problems such as the dissolution of the dispersant in the electrolyte in the battery and an increase in the resistance of the electrolyte.

[0058] [Hydroxyl group-containing structural unit] The hydroxyl group-containing structural unit is a structural unit having a hydroxyl group, and may be a structural unit having an alkylene structure substituted with a hydroxyl group. The alkylene structure is preferably a linear or branched alkylene structure. The number of hydroxyl groups that the hydroxyl group-containing structural unit has is preferably 1 or 2, more preferably 1. The method of introducing hydroxyl group-containing structural unit into polymer is not particularly limited.For example, the method of preparing polymer by polymerization reaction of monomer having hydroxyl group, or the method of preparing polymer by polymerization reaction of monomer having functional group other than hydroxyl group, and modifying it to hydroxyl group can be mentioned.A reasonable method can be selected from the viewpoint of reactivity and raw material cost.

[0059] Examples of monomers having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycerol mono(meth)acrylate, 4-hydroxyvinylbenzene, 2-hydroxy-3-phenoxypropyl acrylate, and caprolactone adducts of these monomers (the number of moles added is 1 to 5), etc. The monomer containing a hydroxyl group is preferably a hydroxyalkyl (meth)acrylate, more preferably 2-hydroxyethyl (meth)acrylate, and even more preferably 2-hydroxyethyl acrylate.

[0060] As a method for preparing a polymer by polymerization reaction of a monomer having a functional group other than a hydroxyl group and modifying it to a hydroxyl group, for example, there is a method in which the acetyl group of polyvinyl acetate obtained by polymerization of vinyl acetate is saponified with an alkali such as sodium hydroxide to convert it to a hydroxyl group (saponification reaction). The saponification reaction rate (saponification degree) can be controlled as desired by changing the concentration of sodium hydroxide and the treatment time.

[0061] For the purpose of increasing the affinity between the carbon nanotube and the medium, at least a part of the hydroxyl groups in the polymer may be reacted with an aldehyde compound to be modified into acetal groups (acetalization).

[0062] The aldehyde compound used in the acetalization reaction may be, for example, a linear, branched, cyclic saturated, unsaturated, or aromatic aldehyde compound having 1 to 15 carbon atoms, but is not limited thereto. Specific examples include formaldehyde, acetaldehyde, propionyl aldehyde, n-butyl aldehyde, isobutyl aldehyde, tert-butyl aldehyde, benzaldehyde, and cyclohexyl aldehyde. These aldehyde compounds may be used alone or in combination of two or more. In addition, these aldehyde compounds may have one or more hydrogen atoms substituted with halogen or the like, except for formaldehyde. From the viewpoint of versatility, linear, branched, cyclic saturated, unsaturated, or aromatic aldehyde compounds having 1 to 10 carbon atoms are preferred, and linear aldehyde compounds having 1 to 4 carbon atoms are more preferred. By changing the aldehyde compound used and the treatment time, the reaction rate of acetalization (degree of acetalization) can be controlled as desired.

[0063] From the viewpoint of strengthening polarization, increasing affinity to carbon nanotubes and a medium, and resistance to an electrolyte, the content of the hydroxyl group-containing structural unit is preferably 3% by mass or more, more preferably 5% by mass or more, when the mass of the polymer is 100% by mass, while it is preferably 20% by mass or less, more preferably 10% by mass or less.

[0064] When the hydroxyl group-containing structural unit is acetalized to have an acetal group, the content of the acetal group-containing structural unit is, for the same reason, preferably 3% by mass or more, more preferably 5% by mass or more, based on 100% by mass of the polymer, and is preferably 20% by mass or less, more preferably 10% by mass or less.

[0065] Furthermore, when one or more selected from the group consisting of nitrile group-containing structural units and heterocyclic ring-containing structural units are contained, the content of hydroxyl group-containing structural units is preferably 1% by mass or more, more preferably 3% by mass or more. On the other hand, it is preferably 10% by mass or less, more preferably 5% by mass or less. By adjusting it to the above range, it is possible to strengthen the polarization and increase the affinity to carbon nanotubes and the medium. It is also preferable from the viewpoint of resistance to the electrolyte. It is particularly preferred that the polymer further contains at least one selected from the group consisting of a nitrile group-containing structural unit and a heterocycle-containing structural unit, since this provides stronger polarization.

[0066] [Heterocyclic structural unit] The heterocyclic ring-containing structural unit is a structural unit having a heterocyclic ring, and may be a structural unit having an alkylene structure substituted by a substituent having a heterocyclic ring. The alkylene structure is preferably a linear or branched alkylene structure. The heterocyclic ring contained in the heterocyclic ring-containing structural unit may be a monocyclic structure or a condensed ring structure, but is preferably a monocyclic structure. In addition, the number of heterocyclic rings contained in the heterocyclic ring-containing structural unit is preferably one or two, more preferably one. The heterocycle contains an atom other than carbon among the atoms constituting the ring, for example, one or more nitrogen atoms, oxygen atoms, sulfur atoms, etc. As the atom other than carbon constituting the ring, a nitrogen atom or an oxygen atom is preferable, and a nitrogen atom is more preferable. By containing an atom other than carbon among the atoms constituting the ring, polarization occurs within the heterocycle, which can have a strong effect on the carbon nanotube. The method for introducing a heterocycle into a polymer is not particularly limited, and for example, a method for preparing a polymer by a polymerization reaction of a monomer having a heterocycle can be used.

[0067] As the monomer having a heterocycle, an N-vinyl cyclic amide structural unit is preferred, and examples thereof include N-vinyl-2-pyrrolidone, N-vinyl-ε-caprolactam, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinedione. In particular, N-vinyl-2-pyrrolidone is preferred from the viewpoint of improving battery characteristics. These may be used alone or in combination of two or more kinds.

[0068] The content of the heterocycle-containing structural unit is preferably 3% by mass or more, more preferably 5% by mass or more, when the mass of the polymer is taken as 100% by mass, from the viewpoint of strengthening the polarization and enhancing the action on the carbon nanotube as described above, while it is preferably 20% by mass or less, more preferably 15% by mass or less. However, when at least one of a nitrile group-containing structural unit and a hydroxyl group-containing structural unit is further contained, the content of the heterocycle-containing structural unit is preferably 1% by mass or more, more preferably 3% by mass or more, based on the mass of the polymer, and is preferably 20% by mass or less, more preferably 15% by mass or less. It is more preferable that the polymer further contains at least one of a nitrile group-containing structural unit and a hydroxyl group-containing structural unit, since this increases the polarity and improves the resistance to the electrolyte.

[0069] [Other structural units] The polymer may further have, as other structural units, one or more structural units selected from the group consisting of active hydrogen group-containing structural units (excluding carboxyl groups and hydroxyl groups), basic group-containing structural units, and ester group-containing structural units. The carbon nanotube dispersion composition of the present embodiment can be easily applied to various uses by selecting and containing the above structural units according to the properties such as hydrophilicity, hydrophobicity, acidity, and basicity of the substrate to which the carbon nanotube dispersion composition of the present embodiment is applied or the material to be mixed.

[0070] The content of the other structural units is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, from the viewpoint of not impairing the polarization of the dispersant, when the mass of the polymer is 100% by mass.

[0071] The active hydrogen group-containing structural unit is a structural unit having, for example, a primary amino group, a secondary amino group, a mercapto group, etc. as an active hydrogen group. Here, "primary amino group" means -NH2 (amino group), and "secondary amino group" means a group in which one hydrogen atom on a primary amino group is replaced with an organic residue such as an alkyl group. However, the primary amino group and the secondary amino group in acid amide are not included in the active hydrogen group in this specification.

[0072] The basic group-containing structural unit is a structural unit having a basic group. Examples of the basic group include tertiary amino group, amide group, etc. In addition, the structural unit having a primary amino group and the structural unit having a secondary amino group are also included in the basic group-containing structural unit. However, in the present disclosure, they are treated as the active hydrogen group-containing structural unit, and are not included in the basic group-containing structural unit.

[0073] The ester group-containing structural unit is (R 1 )2C=C-CO-OR 2 In the above formula, R 1 R is a hydrogen atom or a methyl group, and at least one of them is a hydrogen atom. 2represents an alkyl group which may have a substituent. Incidentally, those containing the above active hydrogen group or the above basic group as a substituent of an alkyl group are treated as the above active hydrogen group-containing structural unit or the above basic group-containing structural unit, and are not included in the ester group-containing structural unit.

[0074] In one embodiment, the combination of structural units contained in the polymer is preferably one or more types selected from the group consisting of only carboxyl group-containing structural units, and carboxyl group-containing structural units / nitrile group-containing structural units, hydroxyl group-containing structural units, and heterocyclic ring-containing structural units, and is preferably one type selected from the group consisting of only carboxyl group-containing structural units, carboxyl group-containing structural units / nitrile group-containing structural units, and carboxyl group-containing structural units / nitrile group-containing structural units / hydroxyl group-containing structural units. Among these, it is preferable to have only a carboxyl group-containing structural unit or a combination of a carboxyl group-containing structural unit and a nitrile group-containing structural unit.

[0075] The method for producing the polymer is not particularly limited. Examples of the method include solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, and precipitation polymerization. Among these, solution polymerization or precipitation polymerization is preferred. Examples of the polymerization reaction system include addition polymerization such as ionic polymerization, free radical polymerization, and living radical polymerization. Among these, free radical polymerization or living radical polymerization is preferred. Examples of the radical polymerization initiator include peroxides and azo-based initiators.

[0076] In the case of carrying out radical polymerization, examples of the polymerization initiator include, but are not limited to, the following: Organic peroxides such as di-t-butyl peroxide, lauroyl peroxide, stearyl peroxide, benzoyl peroxide, t-butyl peroxy neodecane, t-butyl peroxy pivalate, dilauroyl peroxide, dicumyl peroxide, t-butyl peroxy-2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, and 1,1-bis(t-butylperoxy)cyclohexane; Common azo-based radical polymerization initiators such as azobisisobutyronitrile, azobisisovaleronitrile, 1,1-azobis(1-cyclohexanecarbonitrile), 2,2'-azobis-4-methoxy-2,4-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, and 2,2'-azobis-2-methylbutyronitrile. These may be used alone or in combination of two or more. These radical polymerization initiators may be used in combination with a suitable reducing agent as a redox initiator.

[0077] These polymerization initiators are generally used in an amount of 1 part by mass or less per 100 parts by mass of the total mass of all monomers used. The amount of the polymerization initiator can be appropriately selected taking into consideration the temperature at which the polymerization is carried out and the half-life of the polymerization initiator.

[0078] In the process of producing a polymer, the molecular weight of the produced polymer can be controlled using a chain transfer agent or the like within a range that does not impair the object of the present invention. Examples of the chain transfer agent include alkyl mercaptans such as octyl mercaptan, nonyl mercaptan, decyl mercaptan, dodecyl mercaptan, and 3-mercapto-1,2-propanediol, thioglycolic acid esters such as octyl thioglycolate, nonyl thioglycolate, and 2-ethylhexyl thioglycolate, 2,4-diphenyl-4-methyl-1-pentene, 1-methyl-4-isopropylidene-1-cyclohexene, α-pinene, and β-pinene. From the viewpoint of handling and stability, 3-mercapto-1,2-propanediol, thioglycolic acid esters, 2,4-diphenyl-4-methyl-1-pentene, 1-methyl-4-isopropylidene-1-cyclohexene, α-pinene, β-pinene, and the like are particularly preferred. When the above compounds are used, the obtained polymer is also preferred in that it has a low odor. In one embodiment, it is preferred to use one of the above compounds alone or two or more of them in combination as the chain transfer agent. The chain transfer agent can be appropriately added depending on the required molecular weight. In general, it is preferable to use the chain transfer agent in an amount of 0.001 to 4 parts by mass relative to 100 parts by mass of the total mass of all monomers used. In one embodiment, the amount of the chain transfer agent is preferably 0.01 to 4 parts by mass, more preferably 0.1 to 2 parts by mass. By setting the amount of the chain transfer agent in the above range, the molecular weight of the polymer used as the dispersant in this embodiment can be easily adjusted to a suitable range.

[0079] Other molecular weight control methods include a method of changing the polymerization method, a method of adjusting the amount of a polymerization initiator, a method of changing the polymerization temperature, etc. These molecular weight control methods may be used alone or in combination of two or more methods.

[0080] The molecular weight can be measured, for example, by gel permeation chromatography (GPC) equipped with an RI detector and a UV detector (210 nm) in the following manner. A specific example of an apparatus that can be used for the measurement is HLC-8320GPC (manufactured by Tosoh Corporation), and the measurement can be carried out as follows. Separation column: The following are arranged in series in this order: TSKgel Guardcolumn PWXL(6.0mmI.D.×4cm) Two tubes of TSKgel GMPXL (7.8mm I.D. x 30cm) Column temperature: 40℃ Eluent: 0.2M phosphate buffer (pH 7.0) ·Flow rate: 1.0mL / min The sample is prepared in a mixture of the above eluents at a concentration of 0.1% by mass, and 0.1 mL is injected. The molecular weight is calculated as a conversion value using the standard PEO / PEG (Aglient Technologies).

[0081] In some embodiments, the acid value of the dispersant containing a carboxyl group-containing structural unit may be preferably 400 mgKOH / g to 800 mgKOH / g, more preferably 500 mgKOH / g to 800 mgKOH / g, and even more preferably 600 mgKOH / g to 800 mgKOH / g. When the acid value of the dispersant is within the above range, the adsorption to CNTs can be easily increased, and good solubility in the solvent that serves as the dispersion medium can be easily obtained, so that it tends to be easy to maintain a good dispersion state. The dispersion medium (solvent) contains water, and may further contain another medium that has affinity with water, if necessary. When the acid value of the dispersant is less than 400 mgKOH / g, the COO - The dispersion stability is likely to be poor due to the decrease in the number of charge repulsion sites. On the other hand, if the acid value of the dispersant exceeds 900 mg KOH / g, it may cause corrosion of the equipment used during the dispersion process. The acid value is a value measured according to the Japanese Industrial Standard "K0070:1992. Test methods for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemical products" and indicates the amount (mg) of potassium hydroxide required to completely neutralize 1 g of resin component.

[0082] In the carbon nanotube dispersion composition, the above polymer functions as a dispersant. From this viewpoint, it is preferable that the content of the dispersant (B) in the carbon nanotube dispersion composition is determined according to the specific surface area and wettability of the carbon nanotubes. In one embodiment, the content of the dispersant (B) is preferably 15 parts by mass or more, more preferably 20 parts by mass or more, relative to 100 parts by mass of the carbon nanotubes, while being preferably 160 parts by mass or less, more preferably 140 parts by mass or less, and even more preferably 90 parts by mass or less. If it is equal to or greater than the lower limit, the amount of dispersant becomes appropriate, and the occurrence of aggregation of carbon nanotubes is further suppressed, whereas if it is equal to or less than the upper limit, it is preferable to prevent a decrease in fluidity due to an increase in viscosity of the dispersion composition caused by an excessive amount of polymer components, and to suppress the occurrence of deterioration in storage stability. The content of dispersant (B) has an appropriate amount according to the specific surface area of ​​the carbon nanotubes, and it is preferable to increase the amount of dispersant within a preferred range as the specific surface area increases. For example, when the BET specific surface area of ​​the carbon nanotubes used as the raw material is 100 m by nitrogen adsorption measurement, 2 / g or more 1200m 2 / g or less, the content of the dispersant (B) is preferably 15 to 160 parts by mass with respect to 100 parts by mass of the carbon nanotubes.

[0083] <Solvent (C)> The dispersion composition of the present embodiment contains a solvent. The solvent is not particularly limited, but includes water, and may further include other medium having affinity with water, if necessary. Other media that are compatible with water include ethanol, propanol, isopropanol, butanol, octyl alcohol, hexadecyl alcohol, acetylene alcohol, ethylene glycol monobutyl ether, methyl cellosolve, butyl cellosolve, propylene glycol monomethyl ether, acetylene glycol, polyoxyalkylene glycol, propylene glycol, and other glycols.

[0084] <Basic Compound (D)> The dispersion composition of this embodiment can be applied to obtain a desired pH value by any method, but a basic compound can be preferably used. Therefore, in one embodiment, the dispersion composition contains a basic compound (D). By containing the basic compound (D), the dispersion composition interacts with the carboxyl group of the dispersant (B) through strong polarization, generating an electric repulsive force, and the fluidity and storage stability of the dispersion composition can be easily improved. Examples of the basic compound (D) to be added include inorganic bases, inorganic metal salts, organic bases, and organic base salts. Among these, inorganic bases or inorganic metal salts with larger polarization are preferred because they can be effective with a small amount of addition.

[0085] The basic compound may be added during dispersion, or may be added immediately after completion of dispersion and thoroughly mixed and stirred before use. Among these, when the basic compound is added during dispersion, it is preferred because the dispersion speed of the dispersant (B) can be increased.

[0086] Examples of inorganic bases and inorganic metal salts include chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, borates, and ammonium hydroxide of alkali metals or alkaline earth metals. Among these, hydroxides, carbonates, and alkoxides of alkali metals or alkaline earth metals are preferred from the viewpoint of easy supply of cations.

[0087] Examples of the hydroxide of an alkali metal include lithium hydroxide, sodium hydroxide, and potassium hydroxide. Examples of the carbonate of an alkali metal include sodium carbonate and potassium carbonate. Examples of the hydroxide of an alkaline earth metal include calcium hydroxide and magnesium hydroxide. Among these, it is more preferable to use at least one selected from the group consisting of sodium hydroxide, sodium carbonate, potassium hydroxide, and potassium carbonate. The metal contained in the inorganic base may be a transition metal.

[0088] Examples of the alkoxide of an alkali metal include lithium methoxide, lithium ethoxide, lithium-n-butoxide, lithium-t-butoxide, potassium methoxide, potassium ethoxide, potassium-n-butoxide, potassium-t-butoxide, sodium methoxide, sodium ethoxide, sodium-n-butoxide, and sodium-t-butoxide. The number of carbon atoms of the alkoxide may be 5 or more. In particular, sodium-t-butoxide is preferable.

[0089] Examples of the alkoxide of an alkaline earth metal include magnesium methoxide, magnesium ethoxide, magnesium n-butoxide, magnesium t-butoxide, etc. The number of carbon atoms of the alkoxide may be 5 or more.

[0090] Among these, lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, lithium t-butoxide, potassium t-butoxide, and sodium t-butoxide are more preferred, sodium hydroxide, sodium carbonate, potassium hydroxide, and potassium carbonate are even more preferred, and sodium hydroxide and sodium carbonate are most preferred. Note that, in this embodiment, the metal contained in the inorganic base and the inorganic metal salt may be a transition metal.

[0091] Examples of the organic base include primary, secondary and tertiary amine compounds having 1 to 40 carbon atoms which may have a substituent (eg, alkylamines, amino alcohols, etc.), organic hydroxides, and organic metal salts.

[0092] Examples of the organic base include primary, secondary and tertiary alkylamines having 1 to 40 carbon atoms and an optionally substituted alkyl group, and compounds containing the basic nitrogen atom thereof.

[0093] Examples of primary alkylamines having 1 to 40 carbon atoms and an optionally substituted alkyl group include propylamine, butylamine, isobutylamine, octylamine, 2-ethylhexylamine, laurylamine, stearylamine, oleylamine, 2-aminoethanol, 3-aminopropanol, 3-ethoxypropylamine, and 3-lauryloxypropylamine.

[0094] Examples of secondary alkylamines having 1 to 40 carbon atoms and an optionally substituted alkyl group include dibutylamine, diisobutylamine, N-methylhexylamine, dioctylamine, distearylamine, and 2-methylaminoethanol.

[0095] Examples of tertiary alkylamines having 1 to 40 carbon atoms and an optionally substituted alkyl group include triethylamine, tributylamine, N,N-dimethylbutylamine, N,N-diisopropylethylamine, dimethyloctylamine, tri-n-butylamine, dimethylbenzylamine, trioctylamine, dimethyldecylamine, dimethyllaurylamine, dimethylmyristylamine, dimethylpalmitylamine, dimethylstearylamine, dilaurylmonomethylamine, triethanolamine, and 2-(dimethylamino)ethanol.

[0096] Among these, primary, secondary or tertiary alkylamines having 1 to 30 carbon atoms and an optionally substituted alkyl group are preferred, and primary, secondary or tertiary alkylamines having 1 to 20 carbon atoms and an optionally substituted alkyl group are more preferred. The term "optionally substituted alkyl group" means that a hydrogen atom may be substituted, and examples of the substituent include a hydroxy group.

[0097] Other compounds containing a basic nitrogen atom include, for example, 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), 1,4-diazabicyclo[2.2.2]octane (DABCO), imidazole, and 1-methylimidazole.

[0098] The content of the basic compound (D) is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, based on the mass of the dispersion composition, and is preferably 0.40% by mass or less, more preferably 0.20% by mass or less, and even more preferably 0.15% by mass or less. When the content of the basic compound (D) is 0.01% by mass or more, the effect of storage stability tends to be easily obtained. Also, when the content of the basic compound is 0.40% by mass or less, the dispersant is suppressed from being detached from the carbon nanotube, and further, it is preferable that the dispersant is prevented from causing corrosion of the dispersing device and / or the inside of the battery.

[0099] <Other optional ingredients> If necessary, the carbon nanotube dispersion composition of this embodiment can appropriately contain other carbon-based conductive materials other than the carbon nanotubes (A), such as carbon black, dispersants other than the dispersant (B), binders, surfactants, other additives, etc., within a range that does not impair the object of the present invention. These can be added at any timing, such as before, during, or after dispersion of the dispersion composition, or when preparing a composite slurry.

[0100] The carbon nanotube dispersion composition of this embodiment is not particularly limited as long as it can stably disperse the carbon nanotubes, and when dispersing the carbon nanotubes, in addition to the dispersant (B), a surfactant or other dispersant can be further used.

[0101] [Surfactants] Surfactants are mainly classified into anionic, cationic, nonionic and amphoteric. Depending on the properties required for dispersing carbon nanotubes, a suitable type of dispersant can be used in a suitable amount. When selecting an anionic surfactant, the type is not particularly limited.Specific examples include fatty acid salts, polysulfonates, polycarboxylates, alkyl sulfates, alkylaryl sulfonates, alkylnaphthalenesulfonates, dialkylsulfonates, dialkylsulfosuccinates, alkyl phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkylaryl ether sulfates, naphthalenesulfonic acid formalin condensates, polyoxyethylene alkyl phosphoric acid sulfonates, glycerol borate fatty acid esters, and polyoxyethylene glycerol fatty acid esters, but are not limited thereto.Furthermore, specific examples include sodium dodecylbenzenesulfonate, sodium lauric acid sulfate, sodium polyoxyethylene lauryl ether sulfate, polyoxyethylene nonylphenyl ether sulfate, and β-naphthalenesulfonic acid formalin condensates. Examples of suitable salts of the compound include, but are not limited to, sodium salts of the compound.

[0102] In addition, the cationic surfactant includes alkylamine salts and quaternary ammonium salts.Specific examples include, but are not limited to, stearylamine acetate, trimethyl coconut ammonium chloride, trimethyl beef tallow ammonium chloride, dimethyldioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkyl mercaptopyridine, poly(vinylpyridine)-dodecyl bromide and dodecylbenzyl triethyl ammonium chloride.In addition, the amphoteric surfactant includes, but is not limited to, amino carboxylate salts.

[0103] Examples of nonionic surfactants include, but are not limited to, polyoxyethylene alkyl ethers, polyoxyalkylene derivatives, polyoxyethylene phenyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, and alkyl allyl ethers.Specific examples include, but are not limited to, polyoxyethylene lauryl ethers, sorbitan fatty acid esters, and polyoxyethylene octylphenyl ethers.

[0104] The surfactant to be selected is not limited to a single surfactant. Therefore, it is possible to use a combination of two or more surfactants. For example, a combination of an anionic surfactant and a nonionic surfactant, or a combination of a cationic surfactant and a nonionic surfactant can be used. In this case, it is preferable to use a suitable amount for each surfactant component. As a combination, a combination of an anionic surfactant and a nonionic surfactant is preferable. The anionic surfactant is preferably a polycarboxylate. The nonionic surfactant is preferably polyoxyethylene phenyl ether.

[0105] [Other dispersants] As the dispersant used for dispersing the carbon nanotubes, in addition to the dispersant (B), other dispersants such as a resin-type dispersant can also be used. Specific examples of the resin-type dispersant include fluorine-based resin, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, etc. In particular, polyvinyl alcohol and polyvinyl pyrrolidone are preferred. The molecular weight of the resin-type dispersant is preferably 10,000 to 300,000.

[0106] [Binding agent] The binder is a resin capable of binding substances such as carbon-based conductive materials and other particles, and is added to the dispersion liquid after dispersing the carbon nanotubes. In other words, it has a different role from the dispersant described in this specification. The same binder as the dispersant described above may be used. When the carbon nanotube dispersion composition is used in a secondary battery, the binder is not particularly limited as long as it is one that is usually used in secondary batteries, and can be appropriately selected depending on the purpose. Examples of binders used in secondary batteries include polymers or copolymers containing, as constituent units, ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, or the like; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, and fluororesins; cellulose resins (e.g., carboxymethyl cellulose (CMC)); elastomers such as styrene butadiene rubber and fluororubber; and conductive resins such as polyaniline and polyacetylene. Modified bodies, mixtures, and copolymers of these resins may also be used. Among these, when used as a binder for a positive electrode, polymers or copolymers having fluorine atoms in the molecule, such as polyvinylidene fluoride, polyvinyl fluoride, and tetrafluoroethylene, are preferred from the viewpoint of durability. When used as a binder for a negative electrode, carboxymethyl cellulose, styrene butadiene rubber, polyacrylic acid, and the like, which have good adhesion, are preferred.

[0107] <Method of producing dispersion composition> The method for producing the dispersion composition is to disperse a mixture of carbon nanotubes (A), a dispersant (B), a solvent (C), and, if necessary, a basic compound (D), and to obtain a particle size D at 50% cumulative volume by laser diffraction particle size distribution measurement. 50 The method includes a step I of adjusting the particle size of the mixture to within the range of 0.3 to 7 μm, and a step II of adjusting the pH of the mixture to within the ranges of the following (formula a) and (formula b). In the following (formula a) and (formula b), X is the particle size D at 50% cumulative volume measured by laser diffraction particle size distribution measurement after the above dispersion treatment. 50 [μm] and Y is pH. (Formula a) Y≧-0.149X+4.545 (Formula b) Y≦-0.134X+5.140 In the above-mentioned production method, step I and step II may be carried out consecutively as independent steps, or may be carried out simultaneously without distinction between them. For example, when a basic compound (D) is used as a method for adjusting the pH, step I and step II can be carried out simultaneously.

[0108] Hereinafter, as an example of a method for producing a dispersion composition, a method for dispersing carbon nanotubes in a solvent will be described. The dispersion composition is preferably produced, for example, by dispersing carbon nanotubes (A), a dispersant (B), a solvent (C), and, if necessary, a basic compound (D) by a dispersion device to finely disperse them. Note that the dispersion process can be performed in two or more stages by arbitrarily adjusting the timing of addition of the materials used.

[0109] Examples of the dispersion device include a kneader, a two-roll mill, a three-roll mill, a planetary mixer, a ball mill, a horizontal sand mill, a vertical sand mill, an annular bead mill, an attritor, a high shear mixer, a high pressure homogenizer, and an ultrasonic homogenizer. Among them, in order to finely disperse the carbon nanotubes in the dispersion composition and obtain suitable dispersibility, it is preferable to use a high shear mixer, a high pressure homogenizer, an ultrasonic homogenizer, or a combination of these. In particular, from the viewpoint of promoting wetting of the carbon nanotubes and dissolving coarse particles, it is preferable to use a high shear mixer in the initial dispersion step, and then to disperse the carbon nanotubes while maintaining their aspect ratio, it is preferable to use a high pressure homogenizer. The pressure when using the high pressure homogenizer is preferably 40 to 150 MPa, more preferably 70 to 150 MPa.

[0110] Dispersion methods using a dispersing device include batch dispersion, pass dispersion, circulation dispersion, etc., and any of these methods may be used, or two or more methods may be combined. Batch dispersion is a method in which dispersion is performed using only the dispersing device body without using piping or the like. It is easy to handle, so it is preferable for small-scale production. Pass dispersion is a dispersion method in which the dispersing device body is equipped with a tank that supplies the dispersion liquid (a mixture containing dispersoid and dispersion medium, a precursor of the dispersion composition) through piping, and a tank that receives the dispersion liquid, and the dispersion liquid is passed through the dispersing device body. In addition, circulation dispersion is a method in which the dispersion liquid that has passed through the dispersing device body is returned to the tank that supplies the dispersion liquid, and dispersion is performed while circulating. In either case, the longer the processing time, the more the dispersion progresses, so the pass or circulation can be repeated until the desired dispersion state is achieved, and the processing amount can be increased by changing the size of the tank or the processing time. Pass-type dispersion is preferable in that it is easier to homogenize the dispersion state than circulating dispersion. Circulating dispersion is preferable in that the work and manufacturing equipment are simpler than passing dispersion. In the dispersion process, the disintegration of aggregated particles, the loosening, wetting, stabilization, etc. of carbon nanotubes proceed sequentially or simultaneously, and the final dispersion state differs depending on how they proceed, so it is preferable to manage the dispersion state in each dispersion process by various evaluation methods.

[0111] In the dispersion composition of this embodiment, the carbon nanotube content is preferably 0.3% by mass or more, more preferably 0.4% by mass or more, and even more preferably 0.5% by mass or more, based on 100% by mass of the dispersion composition. Also, it is preferably 6.0% by mass or less, and more preferably 5.0% by mass or less. By making the content equal to or more than the above lower limit, it is possible to suppress the compression by the carbon nanotube dispersion composition in the formulation design of the composite slurry, and by making the content equal to or less than the above upper limit, it is preferable to ensure the fluidity and handleability of the dispersion composition.

[0112] The average outer diameter of the carbon nanotubes in the carbon nanotube dispersion composition of this embodiment is preferably 1 nm to 100 nm, more preferably 1.5 nm to 70 nm, and even more preferably 2 nm to 50 nm. If it is equal to or greater than the lower limit, it is preferable because it can prevent the fibers from breaking and follow the volume change accompanying the absorption and release of lithium ions into and from the active material. If it is equal to or less than the upper limit, the number of fibers relative to the amount added to the electrode is sufficient, which is preferable.

[0113] The average fiber length of the carbon nanotubes in the carbon nanotube dispersion composition of this embodiment is preferably 0.3 μm to 50 μm, more preferably 0.5 μm to 20 μm. If it is equal to or greater than the lower limit, it is preferable because a conductive path between active materials can be sufficiently formed. If it is equal to or less than the upper limit, it is preferable because it is possible to prevent the entanglement of the carbon nanotubes from occurring in the electrode and becoming localized, thereby preventing the deterioration of battery performance.

[0114] The average outer diameter and fiber length of the carbon nanotubes in the dispersion composition are measured by diluting the CNT dispersion composition with a solvent so that the CNT concentration is 0.048% by mass, spraying a few μL of the diluted dispersion composition onto a mica substrate, and then drying the mixture on a hot plate at 100°C to prepare a substrate for observing the CNT fiber length. The solvent used is the same as that used to prepare the CNT dispersion composition. The mica substrate is observed with an SEM and image analysis is performed to measure the average value. The length of the short axis and the length of the long axis of 300 tubes are measured, and the average value is used to calculate the average value.

[0115] The dispersibility of carbon nanotubes in the dispersion composition can be evaluated by the complex modulus and phase angle measured by dynamic viscoelasticity measurement. The complex modulus indicates the hardness of the dispersion composition, and tends to be smaller as the dispersibility of carbon nanotubes is better and the viscosity is lower. However, when the fiber length of the carbon nanotubes is large, even if the carbon nanotubes are uniformly and stably dissolved in the medium, the complex modulus may be a high value due to the structural viscosity of the carbon nanotubes themselves. In one embodiment, the complex modulus of the dispersion composition is preferably 5 Pa or more, more preferably 10 Pa or more, at 25° C. and 1 Hz. In addition, it is preferably less than 300 Pa, more preferably less than 60 Pa. By setting the complex elastic modulus of the dispersion composition within the above range, even if the carbon-based conductive material has a long fiber length, such as carbon nanotubes, it is possible to obtain a dispersion composition of the carbonaceous conductive material in which the length is maintained at a certain level or more and the carbonaceous conductive material is uniformly and well dispersed.

[0116] The phase angle means the phase shift of the stress wave when the strain applied to the dispersion composition is a sine wave. If it is a pure elastic body, the sine wave will be in phase with the applied strain, and the phase angle will be 0°. On the other hand, if it is a pure viscous body, the stress wave will be 90° advanced. In a typical viscoelasticity measurement sample, the phase angle will be a sine wave greater than 0° and less than 90°, and if the dispersibility of the carbon nanotubes in the dispersion composition is good, the phase angle will approach 90°, which is the case for a pure viscous body. However, similarly to the complex elastic modulus, when the carbon nanotube itself has structural viscosity, the phase angle may be a low value even if the carbon nanotube is uniformly and stably dissolved in the medium. From this viewpoint, in one embodiment, the phase angle at 25°C and 1 Hz by dynamic viscoelasticity measurement of the dispersion composition is preferably 3° or more, more preferably 5° or more, and even more preferably 10° or more. In addition, it is preferably less than 60°, and more preferably 50° or less. By setting the phase angle of the dispersion composition within the above range, even if the carbon-based conductive material has a long fiber length, such as carbon nanotubes, it is possible to obtain a dispersion composition of the carbon-based conductive material in which the length is maintained at a certain level or more and the carbon-based conductive material is uniformly and well dispersed.

[0117] By uniformly and well dispersing carbon nanotubes with a large fiber length while maintaining the length at a certain level, a developed conductive network is formed. Therefore, it is not enough that the viscosity of the carbon nanotube dispersion composition is low and the (apparent) dispersibility is good, but it is important to judge the dispersion state by combining either or both of the complex modulus and phase angle with conventional indicators such as viscosity. Of these, it is particularly important to consider the phase angle as a major factor. From this perspective, by setting the complex modulus and phase angle in the above ranges, a carbon nanotube dispersion composition with good conductivity and electrode strength can be easily obtained. The complex modulus and phase angle of the carbon nanotube dispersion composition can be measured by the method described in the examples.

[0118] The viscosity of the dispersion composition of the present embodiment was measured using a rheometer at a shear rate of 1 (s -1 When measured at a shear rate of 10 (s), the viscosity is preferably 5 Pa·s or more, more preferably 10 Pa·s or more, and even more preferably 20 Pa·s or more, and is preferably less than 60 Pa·s, and more preferably less than 40 Pa·s. -1 ), the viscosity is preferably 1 Pa s or more and less than 10 Pa. By keeping the viscosity at each shear rate within the above range, the dispersed particle size and dispersed state of the carbon nanotubes can be improved, and the electrode strength and conductivity can be improved.

[0119] The dispersion composition of the present embodiment can be made into a mixture slurry by further adding an active material, and can be used to form an electrode film. In addition, a film formed using the dispersion composition can improve the adhesion between the electrode film and the current collector or the conductivity of the electrode film, and therefore can also be used as a base layer in an electrode.

[0120] <2> Mixture Slurry The composite slurry of the present embodiment can be obtained by adding an active material to the dispersion composition, and can be preferably used for secondary battery electrodes. Since the dispersion composition of this embodiment has excellent fluidity and dispersion stability, a composite slurry in which the carbon nanotubes are uniformly dispersed can be obtained, and the conductive paths can be sufficiently maintained in the formed electrode.

[0121] The active material may be a positive electrode active material or a negative electrode active material. In this specification, the positive electrode active material and the negative electrode active material may be simply referred to as "active material". The active material is a material that is the basis of a battery reaction. The active material is divided into a positive electrode active material and a negative electrode active material based on the electromotive force, and a positive electrode mixture slurry can be obtained by using a positive electrode active material, and a negative electrode mixture slurry can be obtained by using a negative electrode active material. The composite slurry is preferably in a slurry form to improve uniformity and processability.

[0122] If necessary, other optional components may be appropriately contained for the purpose of a binder, wetting, surface activity, pH adjustment, wetting promotion, leveling, conductivity assistance, etc., within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the composite slurry, during mixing, after mixing, or a combination of these.

[0123] For the purpose of better binding the active material and the like, a binder may be added to the dispersion composition.

[0124] The binder used in the production of the composite slurry is not particularly limited as long as it is a polymer component that is usually used as a binder for batteries, and can be appropriately selected according to the purpose. The above-mentioned polyvinylidene fluoride resin that may have a substituent may be used, and other polymer components such as polymers or copolymers having ethylene, propylene, vinyl chloride, vinyl acetate, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, styrene, etc. as constituent components; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins; elastomers such as styrene butadiene rubber and fluororubber; conductive resins such as polyaniline and polyacetylene, etc. may also be used. In addition, modified bodies, mixtures, and copolymers of these resins may be used, and one type may be used alone, or two or more types may be used in combination. These resins can also be used as thickeners.

[0125] The content of CNT in the composite slurry is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and even more preferably 0.05 parts by mass or more, relative to 100 parts by mass of the active material. Also, it is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less. If it is less than the upper limit, it is possible to prevent a decrease in the amount of the active material filled in the electrode and suppress a decrease in the capacity of the battery. Also, if it is more than the lower limit, it is preferable because the conductivity of the electrode and the battery is sufficient.

[0126] The content of the binder in the composite slurry is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, relative to 100 parts by mass of the active material. By making it equal to or more than the lower limit, the adhesion of the conductive film can be further improved. Also, it is preferably 20 parts by mass or less, more preferably 10 parts by mass or less. By making it equal to or less than the upper limit, the active material concentration of the conductive film can be increased, and a higher capacity can be achieved.

[0127] <Positive electrode active material> The positive electrode active material is not particularly limited. For example, for secondary battery applications, metal compounds such as metal oxides and metal sulfides capable of reversibly doping or intercalating lithium ions can be used. For example, lithium manganese composite oxides (such as Li x Mn2O4 or Li x MnO2), lithium nickel composite oxides (such as Li x NiO2), lithium cobalt composite oxides (Li x CoO2), lithium nickel cobalt composite oxides (such as Li x Ni 1-y Co y O2), lithium manganese cobalt composite oxides (such as Li x Mn y Co 1-y O2), lithium nickel manganese cobalt composite oxides (such as Li x Ni y Co z Mn 1-y-z O2), spinel-type lithium manganese nickel composite oxides (such as Li x Mn 2-y Ni y O4), etc., composite oxide powders of lithium and transition metals, lithium phosphate powders having an olivine structure (such as Li x FePO4, Li x Fe 1-y Mn y PO4, Li x CoPO4, etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxides (such as V2O5, V6O 13 ), transition metal oxide powders such as titanium oxide, iron sulfate (Fe2(SO4)3), transition metal sulfide powders such as TiS2, and FeS, etc. However, x, y, and z are numbers, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and 0 < y + z < 1. These positive electrode active materials can also be used alone or in combination of two or more.

[0128] <Negative electrode active material> The negative electrode active material is not particularly limited. For example, it can be metallic Li capable of reversibly doping or intercalating lithium ions, or an alloy thereof, a tin alloy, a silicon alloy negative electrode, Li x TiO2, Li x Fe2O3, Li x Fe3O4, Li x Metal oxide-based materials such as WO2, conductive polymers such as polyacetylene and poly-p-phenylene, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials can be used. However, x is a number and 0 < x < 1. These negative electrode active materials can be used alone or in combination of two or more. In particular, when using a silicon alloy negative electrode, the theoretical capacity is large On the other hand, since the volume expansion is extremely large, it is preferably used in combination with artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, resin-fired carbon materials, etc.

[0129] Note that the silicon-based active material has a large volume change associated with the absorption and release of lithium ions. Without ensuring a conductive path by carbon nanotubes adjusted to an appropriate particle size, it is difficult to perform good repeated charge and discharge. However, since the dispersion composition of this embodiment is excellent in fluidity and dispersion stability, even when using graphite powder and a silicon-based active material as the negative electrode active material, it is possible to suppress an increase in internal resistance within the electrode and suppress a decrease in charge and discharge capacity.

[0130] <Method for manufacturing the composite slurry> In the method of preparing the composite slurry, when a binder is added to the dispersion composition, the order of adding the binder and the active material is not particularly limited. For example, a method of preparing the composite slurry by adding a binder to the dispersion composition and then adding an active material; a method of preparing the composite slurry by adding an active material to the dispersion composition and then adding a binder; a method of preparing the composite slurry by adding a binder and an active material all at once, etc. may be mentioned. The binder may be added after being dissolved in advance. As a method of preparing the composite slurry, a method of adding a binder to the dispersion composition, then further adding an active material, and performing a stirring process is preferable. The stirring device used for stirring is not particularly limited. The stirring device may be a disperser, a homogenizer, etc.

[0131] The non-volatile content in the composite slurry is preferably 30% by mass or more, more preferably 40% by mass or more, based on the mass of the composite slurry (100% by mass), and is preferably 90% by mass or less, more preferably 85% by mass or less.

[0132] <3> electrode membrane The electrode film is formed by forming the composite slurry into a film shape, and contains at least carbon nanotubes (A), a dispersant (B), and, if necessary, a basic compound (D), and an active material. The electrode film may further contain optional components such as a binder. For example, the electrode film can be obtained by preparing a composite slurry by adding an active material and, if necessary, a binder, etc. to the carbon nanotube dispersion composition described above, and applying or coating the composite slurry. For example, the electrode film can be formed by applying the composite slurry to a current collector and removing volatiles.

[0133] <4> secondary battery A secondary battery according to one embodiment of the present invention includes a positive electrode, a negative electrode, and an electrolyte, and at least one selected from the group consisting of the positive electrode and the negative electrode preferably has an electrode film formed from the composite slurry according to this embodiment. The positive electrode and the negative electrode may further include a current collector. Note that when one of the electrode films of the positive electrode or the negative electrode is an electrode film using the dispersion composition according to this embodiment, the electrode film of the other electrode is not particularly limited and may be a conventionally known electrode film.

[0134] In this embodiment, the structure of the secondary battery is not particularly limited. The secondary battery may typically include a positive electrode, a negative electrode, an electrolyte, and a separator that is provided as necessary. The secondary battery may be in various shapes such as a paper type, a cylindrical type, a button type, a laminated type, etc., depending on the purpose of use.

[0135] <Positive or negative electrode> The positive electrode or negative electrode has an electrode film formed from a composite slurry using the dispersion composition of this embodiment, and a current collector. The electrode film can be formed, for example, by applying the dispersion composition onto a current collector and drying it. The electrode film formed using the positive electrode composite slurry can be used as a positive electrode. The electrode film formed using the negative electrode composite slurry can be used as a negative electrode. In this specification, the film formed using the dispersion composition containing an active material may be referred to as an "electrode composite layer".

[0136] The material and shape of the current collector used to form the electrode film are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. Examples of the material of the current collector include conductive metals or alloys such as aluminum, copper, nickel, titanium, and stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil current collector, and a mesh current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.

[0137] The method of applying the dispersion composition onto the current collector is not particularly limited, and any known method can be used.Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting.The drying method includes, but is not limited to, drying by leaving it to dry, or drying using a blower dryer, a hot air dryer, an infrared heater, or a far infrared heater.

[0138] After coating, rolling treatment may be performed using a lithographic press, a calendar roll, etc. The thickness of the formed film is, for example, from 1 μm to 500 μm, and preferably from 10 μm to 300 μm.

[0139] <Electrolytes> As the electrolyte, various conventionally known electrolytes capable of moving ions can be used. For example, those containing lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto. The electrolyte is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.

[0140] Examples of non-aqueous solvents include, but are not limited to, carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0141] The secondary battery preferably has a separator. Examples of the separator include, but are not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.

[0142] The embodiments of the present invention include the following: However, the present invention is not limited to the following embodiments and includes various forms. [1] A method for producing a dispersion medium comprising the steps of: (A) carbon nanotubes; (B) a dispersant; (C) a solvent; and (D) a basic compound; Particle size D at 50% cumulative volume measured by laser diffraction particle size distribution measurement 50 is 0.3 to 7 μm, A carbon nanotube dispersion composition characterized by satisfying the following (1) and (2): (1) The dispersant (B) is a polymer having a weight-average molecular weight of 5,000 or more and 360,000 or less and having a carboxyl group-containing structural unit, The content of the carboxyl group-containing structural unit is 80 mass % or more based on the mass of the polymer. (2) Particle size D at 50% cumulative volume of the carbon nanotube dispersion composition measured by laser diffraction particle size distribution measurement50 When X [μm] and pH is Y, X and Y satisfy the following (formula a) and (formula b). (Formula a) Y≧-0.149X+4.545 (Formula b) Y≦-0.134X+5.140 [2] The carbon nanotube dispersion composition according to the above [1], wherein the phase angle at 1 Hz at 25°C as determined by dynamic viscoelasticity measurement is 3° or more and less than 60°. [3] The carbon nanotube dispersion composition according to [1] or [2], having a complex modulus of elasticity at 1 Hz at 25°C as measured by dynamic viscoelasticity measurement of 5 Pa or more and less than 300 Pa. [4] The carbon nanotube dispersion composition according to any one of [1] to [3], wherein the content of the dispersant (B) is 15 to 90 parts by mass per 100 parts by mass of the carbon nanotubes (A). [5] The carbon nanotube dispersion composition according to any one of the above [1] to [4], wherein the carboxyl group-containing structural unit is a structural unit derived from (meth)acrylic acid. [6] A composite slurry comprising the carbon nanotube dispersion composition according to any one of the above [1] to [5] and an active material. [7] An electrode film formed from the composite slurry described in [6] above. [8] A secondary battery having a positive electrode and a negative electrode, A secondary battery, wherein at least one of a positive electrode and a negative electrode has the electrode film described in [7] above. EXAMPLES

[0143] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0144] <Average outer diameter of carbon nanotubes> Measurement method: Carbon nanotubes are dispersed in toluene using an ultrasonic homogenizer, then placed on a collodion film and dried. The carbon nanotubes are observed and photographed using a transmission electron microscope (TEM). Next, 100 carbon nanotubes are randomly selected from the observation photograph, and the outer diameter of each is measured. The average outer diameter (nm) of the raw carbon nanotubes is calculated as the number average of the outer diameters.

[0145] <Measurement of the specific surface area of ​​carbon nanotubes> 0.03 g of CNT was weighed out using an electronic balance (MSA225S100DI, manufactured by Sartorius), and then dried for 15 minutes at 110° C. while degassing. Then, the BET specific surface area of ​​the CNT was measured using a fully automatic specific surface area measuring device (HM-model1208, manufactured by MOUNTECH).

[0146] Details of the materials used in the present examples and comparative examples are as follows. <Carbon nanotubes (A)> TUBALL: Single-wall carbon nanotube (OCSiAl, average outer diameter 1.6 nm, specific surface area 980 m 2 / g) ·10B: JENOTUBE10B (manufactured by JEIO, multilayer CNT, average outer diameter 10 nm, specific surface area 233 m 2 / g) ·6A:JENOTUBE6A (manufactured by JEIO, multilayer CNT, average outer diameter 6nm, specific surface area 680m 2 / g) TNSAR: Single-wall carbon nanotube (Timesnano, average outer diameter 1.5 nm, specific surface area 950 m 2 / g) ·BT1001М: (Made by LGC, multilayer CNT, average outer diameter 10nm, specific surface area 260m 2 / g)

[0147] <Basic Compound (D)> D-1: Na2CO3 (sodium carbonate, manufactured by Tokyo Chemical Industry Co., Ltd., purity >99.0%) D-2: NaOH (sodium hydroxide, Tokyo Chemical Industry Co., Ltd., purity >98.0%, granular) D-3: KOH (potassium hydroxide, manufactured by Tokyo Chemical Industry Co., Ltd., purity >86.0%) D-4: CH3COONa (sodium acetate, manufactured by Tokyo Chemical Industry Co., Ltd., purity >98.5%) D-5: K2CO3 (potassium carbonate, manufactured by Tokyo Chemical Industry Co., Ltd., purity >99.0%) D-6: BtONa (sodium t-butoxide, manufactured by Tokyo Chemical Industry Co., Ltd., purity >98.0%)

[0148] <Production of Dispersant (B) etc.> (Dispersant (B-1)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 100 parts of acrylic acid, 0.8 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at a temperature of 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was stopped by cooling. After that, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-necked separable flask was charged with 500 parts of methyl ethyl ketone and 500 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while rotating the flask at 1,000 revolutions in a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B-1)).

[0149] (Dispersant (B-2)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 95 parts of acrylic acid, 5 parts of acrylonitrile, 2.8 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at a temperature of 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was stopped by cooling. After that, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-necked separable flask was charged with 500 parts of methyl ethyl ketone and 500 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while rotating the flask at 1,000 revolutions with a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B-2)).

[0150] (Dispersant (B-3)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 95 parts of acrylic acid, 5 parts of 2-hydroxyethyl acrylate, 0.8 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at a temperature of 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was stopped by cooling. After that, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-necked separable flask was charged with 500 parts of methyl ethyl ketone and 500 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while rotating the flask at 1,000 revolutions with a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B-3)).

[0151] (Dispersant (B-4)) In a reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer, 100 parts of methanol, 0.1 parts of diethanolamine, and 5 parts of sodium hypophosphite were charged and replaced with nitrogen gas. The reaction vessel was heated to 70°C, and 90 parts of acrylic acid and 10 parts of N-vinyl-2-pyrrolidone were added dropwise over 2 hours. Subsequently, an aqueous initiator solution consisting of 2 parts of 2,2'-azobis-2-amidinopropane dihydrochloride (manufactured by Fujifilm Wako Pure Chemical Industries: V-50) and 18 parts of ion-exchanged water was added dropwise over 1.5 hours. After the addition was completed, the mixture was reacted for 3.5 hours, and then an aqueous solution consisting of 0.1 parts of V-50 and 0.9 parts of ion-exchanged water was added, and after another 30 minutes, an aqueous solution consisting of 0.1 parts of V-50 and 0.9 parts of ion-exchanged water was added again. After 4.5 hours from the start of polymerization, it was confirmed that the conversion rate reached 95%, and 0.5 parts of 10% aqueous malonic acid solution was added as a pH adjuster to obtain an aqueous dispersion of the polymer.Then, the polymer was filtered by vacuum filtration, washed with methanol, and the solvent was completely removed by vacuum drying to obtain a polymer (dispersant (B-4)).

[0152] (Dispersant (B-5)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 100 parts of methacrylic acid, 0.8 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at a temperature of 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was terminated by cooling. Thereafter, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-necked separable flask was charged with 500 parts of methyl ethyl ketone and 500 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while the flask was rotated 1,000 times with a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B-5)).

[0153] (Dispersant (B-6)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 90 parts of acrylic acid, 5 parts of acrylonitrile, 5 parts of 2-hydroxyethyl acrylate, 2.8 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at a temperature of 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was terminated by cooling. Thereafter, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-neck separable flask was charged with 500 parts of methyl ethyl ketone and 500 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while the flask was rotated 1,000 times with a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B-6)).

[0154] (Dispersant (B-7)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 95 parts of acrylic acid, 5 parts of methyl acrylate, 0.8 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at a temperature of 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was terminated by cooling. Thereafter, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-necked separable flask was charged with 500 parts of methyl ethyl ketone and 500 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while the flask was rotated 1,000 times with a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B-7)).

[0155] (Dispersant (B-8)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 100 parts of acrylic acid, 6.9 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at a temperature of 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was stopped by cooling. Thereafter, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-necked separable flask was charged with 250 parts of methyl ethyl ketone and 250 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while rotating the flask at 1,000 revolutions in a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B-8)).

[0156] (Dispersant (B-9)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 100 parts of acrylic acid, 1.25 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was stopped by cooling. After that, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-necked separable flask was charged with 250 parts of methyl ethyl ketone and 250 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while rotating the flask at 1,000 revolutions in a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B-9)).

[0157] (Dispersant (B-10)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 80 parts of acrylic acid, 20 parts of acrylamide, 0.55 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at a temperature of 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was terminated by cooling. Thereafter, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-neck separable flask was charged with 500 parts of methyl ethyl ketone and 500 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while the flask was rotated 1,000 times with a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B-10)).

[0158] (Dispersant (B'-1)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 70 parts of acrylic acid, 30 parts of acrylonitrile, 2.8 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at a temperature of 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was terminated by cooling. Thereafter, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-neck separable flask was charged with 500 parts of methyl ethyl ketone and 500 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while the flask was rotated 1,000 times with a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B'-1)).

[0159] (Dispersant (B'-2)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 100 parts of acrylic acid, 9.3 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at a temperature of 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was terminated by cooling. Thereafter, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-necked separable flask was charged with 250 parts of methyl ethyl ketone and 250 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while the flask was rotated at 1,000 revolutions in a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B'-2)).

[0160] (Dispersant (B'-3)) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 100 parts of acrylic acid, 0.03 parts of 3-mercapto-1,2-propanediol, and 0.5 parts of V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the reaction was terminated by cooling. Thereafter, the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. A four-necked separable flask was charged with 250 parts of methyl ethyl ketone and 250 parts of methanol, and the aqueous solution of the polymer was dropped over 1 hour while the flask was rotated 1,000 times with a disperser. The resulting white precipitate was removed by filtration and dried under reduced pressure to obtain a polymer (dispersant (B'-3)).

[0161] The molecular weight of the dispersant (B) was measured by gel permeation chromatography (GPC) equipped with an RI detector and a UV detector (210 nm). Specifically, the molecular weight is as follows. Equipment: HLC-8320GPC (Tosoh) Separation columns: The following were arranged in series in this order. TSKgel Guardcolumn PWXL(6.0mmI.D.×4cm) TSKgel GMPXL (7.8mmI.D.×30cm) 2 pieces Column temperature: 40℃ Eluent: 0.2M phosphate buffer (pH 7.0) ·Flow rate: 1.0mL / min The sample was prepared in a mixture of the above eluents at a concentration of 0.1% by mass, and 0.1 mL was injected. The molecular weight was calculated using the standard PEO / PEG (Aglient Technologies).

[0162] [Table 1]

[0163] <Preparation of Dispersion Composition> (Example 1-1) According to the materials and compositions shown in Table 2, the materials were added in order and a CNT dispersion composition was prepared according to the following method. Into a stainless steel container, 1960.8 parts of ion-exchanged water, 18 parts of the dispersant (B-1), and 1.2 parts of the basic compound (D) were added, and the mixture was stirred with a disperser until homogenized. Then, 20 parts of CNT (TUBALL) was added while stirring with a disperser, and a square hole high shear screen was attached to a high shear mixer (L5M-A, manufactured by Silverson) and batch dispersion was performed at a speed of 8,000 rpm until the entire mixture became uniform and the dispersion particle size measured by the grind gauge was 250 μm or less. At this time, the dispersion particle size measured by the grind gauge was 180 μm. Next, the liquid to be dispersed was fed from the stainless steel container through a pipe to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine Co., Ltd.) to obtain a particle size D 50 The pass-type dispersion process was performed until the particle size D was 0.3 to 7 μm. 50 was 1.5 μm. The dispersion process was performed using a single nozzle chamber with a nozzle diameter of 0.20 mm and a pressure of 150 MPa to obtain carbon nanotube dispersion composition 1 containing 1.0 mass% TUBALL as carbon nanotubes (A), 0.90 mass% dispersant (B-1) as dispersant (B), and 0.06 mass% basic compound (D-1) (Na2CO3) as basic compound (D).

[0164] (Examples 1-2 to 1-28, 1-31 to 1-33, Comparative Examples 1-1 to 1-5) According to the materials and compositions shown in Table 2, the particle size D 50 The dispersion compositions were each subjected to a pass type dispersion treatment until the particle size reached 0.3 to 7 μm (Dispersion Compositions 2 to 28, 31 to 33, and Comparative Dispersion Compositions 1 to 5). The dispersion conditions were: particle size D after 20 passes of dispersion processing 50 If the particle size is 7 μm or more, perform two additional passes of dispersion processing and measure again to determine the particle size D 50 Repeat until the particle size D becomes 7μm or less, and control the number of passes to 50 was adjusted to be 0.3 to 7 μm.

[0165] (Examples 1-29) According to the composition shown in Table 2, a glass bottle (M-225, manufactured by Kashiwa Glass Co., Ltd.) was charged with a dispersant (B-1), a basic compound (D-1), and ion-exchanged water, and after thorough mixing and dissolving or mixing, CNTs were added, and the mixture was dispersed for a total of 8 hours using zirconia beads (bead diameter 0.5 mmφ) as a medium while cooling the glass bottle every 2 hours with a paint conditioner, to obtain a carbon nanotube dispersion composition 29. Particle size D 50 was 3.8 μm.

[0166] (Examples 1-30) According to the composition shown in Table 2, dispersant (B-1), conductive material, and a small amount of ion-exchanged water were charged into a Labo Plastomill (manufactured by Toyo Seiki Seisakusho Co., Ltd.) and dispersed for 3 hours, then transferred to a stainless steel container, the remaining ion-exchanged water and basic compound (D-1) were added, and a high shear mixer (L5M-A, manufactured by Silverson) equipped with a square hole high shear screen was attached, and batch dispersion was performed at a speed of 8,000 rpm until the entire mixture became uniform and the dispersion particle size was 250 μm or less as measured by the grind gauge, thereby obtaining a carbon nanotube dispersion composition 30. At this time, the dispersion particle size confirmed by the grind gauge was 80 μm, and the particle size D 50 was 6.0 μm.

[0167] (Examples 1-34 to 1-36) According to the compositions shown in Table 2 and in the same manner as in Example 1-1, carbon nanotube dispersion compositions 34 to 36 were obtained.

[0168] <Measurement and evaluation of physical properties of dispersion composition> The physical properties of the dispersion composition and the storage stability were evaluated by the following methods. The results are shown in Table 2.

[0169] (Particle size of the dispersed composition D 50 (Method of measurement) Particle size at 50% cumulative volume D 50 was measured using a laser diffraction particle size distribution analyzer (Partical LA-960V2, manufactured by HORIBA). The circulation / ultrasonic operation conditions were: circulation speed: 3, ultrasonic intensity: 7, ultrasonic time: 1 minute, stirring speed: 1, stirring mode: continuous. During air removal, ultrasonic operation was performed with ultrasonic intensity 7 and ultrasonic time 5 seconds. The particle refractive index of the carbon-based conductive material was 1.9, and the shape was aspheric. The refractive index of the solvent was 1.333. During measurement, the concentration of the CNT dispersion composition was diluted so that the transmittance value was in the range of 50 to 85%. The particle size was based on volume.

[0170] (Method for measuring pH of dispersion composition) The pH of the samples was measured at 25°C using a benchtop pH meter (Seven Compact S200 Expert Pro, Mettler Toledo).

[0171] (Complex Modulus and Phase Angle of Dispersion Composition) The complex modulus and phase angle of the dispersion composition were determined by dynamic viscoelasticity measurements using a rheometer (RheoStress1 rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a cone diameter of 35 mm and an angle of 2° at 25°C, a frequency of 1 Hz, and a strain rate range of 0.01% to 5%. The complex elastic modulus is preferably 5 Pa or more and less than 300 Pa, and more preferably 10 Pa or more or less than 60 Pa. The phase angle is preferably equal to or greater than 3° and less than 60°, and more preferably equal to or greater than 10°. The lower the complex modulus of the dispersion composition and the closer the phase angle of the dispersion composition is to 90°, the better the flowability. ·Evaluation criteria for complex modulus 1: 300 Pa or more or less than 5 Pa 2: 60 Pa or more but less than 300 Pa 3: 10 Pa or more but less than 60 Pa 4: 5 Pa or more but less than 10 Pa Phase angle evaluation criteria 1: 10° to less than 60° 2: 3° to less than 10° Less than 3:3°

[0172] (Method for Evaluating Storage Stability of Dispersion Composition) The storage stability was evaluated by determining whether the dispersion composition had fluidity after being left to stand and stored at 40°C. The evaluation method is as follows. The complex modulus was evaluated by performing dynamic viscoelasticity measurement at 25°C, a frequency of 1 Hz, and a strain rate range of 0.01% to 5% using a rheometer (RheoStress1 rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a diameter of 35 mm and a 2° cone. If the evaluation criteria were ◎ to △, the composition was usable. Evaluation criteria ◎: Less than 300 Pa after one month (Excellent) 〇: Reached 300 Pa after 1 month (good) △: Reaches 300 Pa after 1 week (OK) ×: Reach 300Pa after 1 day

[0173] [Table 2-1] [Table 2-1A]

[0174] [Table 2-2] [Table 2-2A]

[0175] <Production and evaluation of secondary batteries> <Preparation of negative electrode mixture slurry and negative electrode> (Example 2-1) A dispersion composition (dispersion composition 1), a thickener, and water were added to a plastic container, and the mixture was stirred at 2,000 rpm for 30 seconds using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310). Then, artificial graphite and silicon (artificial graphite: silicon = 9: 1 (mass ratio)) were added as negative electrode active materials, and the mixture was stirred at 2,000 rpm for 150 seconds using the planetary centrifugal mixer. After that, SBR (styrene butadiene rubber) was added, and the mixture was stirred at 2,000 rpm for 30 seconds using the planetary centrifugal mixer to obtain a negative electrode composite slurry. The active material, CNT, dispersant, thickener, and SBR in the negative electrode mixture slurry were mixed in the amounts (mass%) shown in Table 3 when the total amount was taken as 100 mass%, and the amount of water was adjusted so that the non-volatile content of the negative electrode mixture slurry was 45%. The amounts shown in Table 3 represent the net content (non-volatile content mass%) of each component in the negative electrode mixture slurry.

[0176] The obtained negative electrode composite slurry was applied to a copper foil having a thickness of 20 μm using an applicator, and the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes to produce an electrode film. The electrode film was then rolled using a roll press (3t hydraulic roll press, manufactured by Sun Metals) to obtain a negative electrode (negative electrode 1). The weight per unit area of ​​the composite layer was 10 mg / cm. 2 The density of the composite layer after rolling is 1.6 g / cm 3 It was.

[0177] The above raw materials are as follows: Artificial graphite: CGB-20 (manufactured by Nippon Graphite Industries Co., Ltd.), 100% non-volatile content Silicon: Silicon monoxide (Osaka Titanium Technologies, SILICON MONOOXIDE SiO 1.3C 5μm, non-volatile content 100%) Thickener: CMC (Carboxymethylcellulose, #1190 (manufactured by Daicel Finechem), non-volatile content 100%) Binder: SBR (styrene butadiene rubber, TRD2001 (JSR Corporation), non-volatile content 48%)

[0178] (Examples 2-2 to 2-36) Except for changing the dispersion composition to each dispersion composition (dispersion compositions 2 to 36) shown in Table 3 and changing the composition ratio to that shown in Table 3, a negative electrode composite slurry was produced in the same manner as in Example 2-1, and negative electrodes 2 to 36 were obtained in the same manner.

[0179] (Comparative Examples 2-1 to 2-5) Except for changing the dispersion composition to each dispersion composition (comparative dispersion compositions 1 to 5) shown in Table 3, a comparative negative electrode composite slurry was produced in the same manner as in Example 2-1, and comparative negative electrodes 1 to 5 were obtained in the same manner.

[0180] (Reference Example 2-1: Preparation of standard negative electrode) 0.5% by mass of acetylene black (Denka Black (registered trademark) HS-100, Denka Co., Ltd.), 1% by mass of MAC500LC (carboxymethylcellulose sodium salt Sunrose special type MAC500LC, Nippon Paper Industries Co., Ltd., non-volatile content 100%), and 98.4% by mass of water were added to a 150 ml plastic container, and the mixture was stirred at 2,000 rpm for 30 seconds using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310). Furthermore, 97% by mass of artificial graphite (CGB-20, Nippon Graphite Industries Co., Ltd.) was added as an active material, and the mixture was stirred at 2,000 rpm for 150 seconds using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310). Next, 3.1% by mass of SBR (styrene butadiene rubber, TRD2001, non-volatile content 48%, manufactured by JSR) was added and stirred at 2,000 rpm for 30 seconds using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310) to obtain a standard negative electrode composite slurry. The non-volatile content of the standard negative electrode composite slurry was set to 50% by mass.

[0181] The above-mentioned standard negative electrode composite slurry was applied to a 20 μm-thick copper foil current collector using an applicator, and then dried in an electric oven at 80°C ± 5°C for 25 minutes to obtain an electrode with a coating weight per unit area of ​​10 mg / cm. 2 Further, a rolling process was performed using a roll press (Thank Metals, 3 t hydraulic roll press) to adjust the density of the electrode mixture layer to 1.6 g / cm. 3 A standard negative electrode was prepared.

[0182] [Table 3]

[0183] <Preparation of Positive Electrode Mixture Slurry and Positive Electrode> (Example 3-1) A dispersion composition (dispersion composition 1), a thickener, and water were added to a plastic container, and the mixture was stirred for 30 seconds at 2,000 rpm using a planetary centrifugal mixer (Thinky Corporation, ARE-310, Thinky Corporation). LFP was then added as a positive electrode active material, and the mixture was stirred for 150 seconds at 2,000 rpm using a planetary centrifugal mixer (Thinky Corporation, ARE-310, Thinky Corporation). PTFE was then added as a binder, and the mixture was stirred for 30 seconds at 2,000 rpm using a planetary centrifugal mixer (Thinky Corporation, ARE-310, Thinky Corporation) to obtain a positive electrode composite slurry. The active material, CNT, dispersant, thickener, and binder (PTFE) in the positive electrode mixture slurry were mixed in the amounts (mass%) shown in Table 4 when the total of the nonvolatile contents was taken as 100 mass%, and the amount of water was adjusted so that the nonvolatile content of the positive electrode mixture slurry was 65%. The amounts shown in Table 4 represent the net content (mass% nonvolatile content) of each component in the positive electrode mixture slurry.

[0184] The positive electrode composite slurry was applied onto an aluminum foil having a thickness of 20 μm using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to produce an electrode film. The electrode film was then rolled using a roll press (3 ton hydraulic roll press, manufactured by Sun Metals) to obtain a positive electrode (positive electrode 1). The weight per unit area of ​​the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling was 2.1 g / cc.

[0185] The above raw materials are as follows: LFP: Lithium iron phosphate HED (registered trademark) LFP-400 (manufactured by BASF, 100% non-volatile content) Binder: PTFE (polytetrafluoroethylene, Polyflon PTFE D-210C (manufactured by Daikin Industries, non-volatile content 60%) Thickener: CMC (Carboxymethylcellulose #1190 (manufactured by Daicel Finechem, 100% non-volatile content)

[0186] (Examples 3-2 to 3-36) Positive electrodes 2 to 36 were obtained in the same manner as in Example 3-1, except that the conductive material dispersion was changed to each dispersion composition shown in Table 4 (dispersion compositions 2 to 36).

[0187] (Comparative Examples 3-1 to 3-5) Comparative positive electrodes 1 to 5 were obtained in the same manner as in Example 3-1, except that the conductive material dispersion was changed to each dispersion composition shown in Table 4 (comparative dispersion compositions 1 to 5).

[0188] (Reference Example 3-1: Preparation of standard positive electrode) As the positive electrode active material, 92% by mass of LFP (HED (trademark) LFP-400, manufactured by BASF, 100% non-volatile content), 4% by mass of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka, 100% non-volatile content), and 1.6% by mass of thickener (carboxymethylcellulose #1190, manufactured by Daicel FineChem, 100% non-volatile content) were added to a plastic container, and then mixed until uniform using a spatula. Then, 20.5% by mass of water was added, and the mixture was stirred at 2,000 rpm for 30 seconds using a rotation-revolution mixer (Thinky Corporation, Awatori Rentaro, ARE-310). Then, the mixture in the plastic container was mixed until uniform using a spatula, and 4% by mass of PTFE (manufactured by Daikin Industries, 60% non-volatile content) was added using a rotation-revolution mixer, and the mixture was stirred at 2,000 rpm for 30 seconds. After that, 11.2 mass % of water was added, and the mixture was stirred at 2,000 rpm for 30 seconds using the planetary centrifugal mixer, and finally, stirred at 3,000 rpm for 10 minutes using a high-speed stirrer to obtain a standard positive electrode composite slurry.

[0189] The standard positive electrode composite slurry was applied to an aluminum foil having a thickness of 20 μm using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to prepare an electrode film. The electrode film was then rolled using a roll press (3 ton hydraulic roll press, manufactured by Sun Metals) to obtain a standard positive electrode. The weight per unit area of ​​the electrode composite layer was 20 mg / cm. 2 The density of the electrode mixture layer after rolling was 2.1 g / cc.

[0190] [Table 4]

[0191] (Secondary battery production) Using the standard positive electrode and the negative electrode or the comparative negative electrode shown in Table 5, or the positive electrode or the comparative positive electrode and the standard negative electrode shown in Table 6, each was punched out to 50 mm x 45 mm and 45 mm x 40 mm, and the punched positive electrode and the negative electrode and the separator (porous polypropylene film) inserted therebetween were inserted into an aluminum laminate bag and dried in an electric oven at 70 ° C. for 1 hour. Then, in a glove box filled with argon gas, 2 mL of electrolyte (a non-aqueous electrolyte in which ethylene carbonate, dimethyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:1:1, and further vinylene carbonate was added as an additive at 1 mass% to 100 mass%, and LiPF6 was dissolved at a concentration of 1M) was injected, and the aluminum laminate was sealed to prepare a secondary battery.

[0192] <Evaluation of secondary batteries> The obtained secondary battery was evaluated by the following methods. The results are shown in Tables 5 and 6. (Method of evaluating rate characteristics of secondary batteries) The same procedure was carried out as in paragraph 0178 of Patent No. 7107413. If the evaluation criteria are ⊚ to △, the product is practical. ·Rate characteristic evaluation criteria ◎: 90% or more (excellent) ○: 85% or more but less than 90% (good) △: 80% or more but less than 85% (acceptable) ×: Less than 80%

[0193] (Method of evaluating cycle characteristics of secondary batteries) The same procedure was carried out as in paragraph 0179 of Japanese Patent No. 7107413. If the evaluation criteria were ⊚ to △, the product was practical. · Evaluation criteria for cycle characteristics ◎: 90% or more (excellent) ○: 80% or more but less than 90% (good) △: 70% or more but less than 80% (acceptable) ×: Less than 70%

[0194] [Table 5]

[0195] [Table 6]

[0196] As can be seen from Tables 2, 5, and 6, the polymer containing 80% by mass or more of a carboxyl group-containing structural unit and a basic compound is used, and the particle size D 50 It was confirmed that the dispersion composition adjusted to an appropriate pH value was able to achieve a balance between fluidity, storage stability, and battery performance. Particle size D of carbon nanotube dispersion composition 50 When adjusting the particle size to 0.3 to 7.0 μm, dispersion with dispersant (B), which is a polymer having a weight-average molecular weight of 5,000 or more and 360,000 or less and having a carboxyl group-containing structural unit, could be applied by adjusting the pH, regardless of the type of carbon nanotube or the type of basic compound. As in the comparative example, when the pH was low or a polymer with a low content of carboxyl group-containing structural units was used, the fluidity was poor due to insufficient charge repulsion of the carboxyl groups, and when the pH was high, the affinity between the polymer and the carbon nanotubes decreased and thickening occurred due to aggregation of the carbon nanotubes. When the dispersant was a polymer with a low molecular weight, the fluidity was poor due to insufficient steric repulsion, and when the dispersant was a polymer with a high molecular weight, thickening occurred due to the viscosity of the polymer itself.

[0197] Although the present invention has been described above with reference to the embodiment, the present invention is not limited to the above. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the invention.

Claims

1. A dispersion medium comprising carbon nanotubes (A), a dispersant (B), and a solvent (C), Particle size D at 50% cumulative volume measured by laser diffraction particle size distribution measurement 50 is 0.3 to 7 μm, A carbon nanotube dispersion composition characterized by satisfying the following (1) and (2): (1) The dispersant (B) is a polymer having a weight average molecular weight of 5,000 or more and 360,000 or less, and having a carboxyl group-containing structural unit derived from at least one of (meth)acrylic acid and a (meth)acrylate having a carboxyl group, The content of the carboxyl group-containing structural unit is 80 mass % or more based on the mass of the polymer. (2) Particle size D at 50% cumulative volume of the carbon nanotube dispersion composition measured by laser diffraction particle size distribution measurement 50 When X [μm] and pH is Y, X and Y satisfy the following (formula a) and (formula b). (Formula a) Y≧-0.149X+4.545 (Formula b) Y≦-0.134X+5.140

2. The carbon nanotube dispersion composition according to claim 1 , further comprising a basic compound (D).

3. 3. The carbon nanotube dispersion composition according to claim 1, wherein a phase angle at 1 Hz at 25° C. as determined by dynamic viscoelastic measurement is equal to or greater than 3° and less than 60°.

4. 4. The carbon nanotube dispersion composition according to claim 1, wherein the complex modulus at 1 Hz at 25° C. as determined by dynamic viscoelasticity measurement is 5 Pa or more and less than 300 Pa.

5. The carbon nanotube dispersion composition according to any one of claims 1 to 4, wherein the content of the dispersant (B) is 15 to 160 parts by mass per 100 parts by mass of the carbon nanotubes (A).

6. The carbon nanotube dispersion composition according to any one of claims 1 to 5, wherein the content of the dispersant (B) is 15 to 90 parts by mass per 100 parts by mass of the carbon nanotubes (A).

7. The carbon nanotube (A) has a BET specific surface area of ​​100 m as measured by nitrogen adsorption. 2 / g or more 1200m 2 The carbon nanotube dispersion composition according to any one of claims 1 to 6, wherein the average molecular weight of the carbon nanotube dispersion composition is 100% or less.

8. The carbon nanotube dispersion composition according to any one of claims 1 to 7, wherein the carboxyl group-containing structural unit is a structural unit derived from (meth)acrylic acid.

9. A composite slurry comprising the carbon nanotube dispersion composition according to any one of claims 1 to 8 and an active material.

10. An electrode film formed from the composite slurry according to claim 9.

11. A secondary battery including a positive electrode and a negative electrode, A secondary battery, wherein at least one of a positive electrode and a negative electrode has the electrode film according to claim 10.

Citation Information

Patent Citations

  • Composition containing carbon nanotubes and method of adjusting the same, and composite matter formed of the composition and method of manufacturing the same

    JP2004167667A

  • Carbon nanotube dispersion and use thereof

    WO2022075387A1

  • Carbon nanotubes, carbon nanotube dispersion liquid, and nonaqueous electrolyte secondary battery using same

    WO2023127931A1

  • Carbon nanotube dispersion and nonaqueous electrolyte secondary battery

    JP2015195143A

  • Water dispersion of carboxymethylcellulose sodium containing multilayer carbon nanotube

    JP2016028109A